Metal acid compound dispersion and method for producing the same

By adding specific metals and alkali metals to the metallic acid composite and controlling the particle size, the soluble and stability problems of metallic acid composites in the prior art are solved, and efficient film formation and material application are achieved.

JP2025039502APending Publication Date: 2025-03-21MITSUI MINING & SMELTING CO LTD

Patent Information

Application Number
JP2024034991
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-08
Filing Date
2024-03-07
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, lithium metallic acids have problems with low solubility, instability and difficulty in forming uniform films in the preparation of nonlinear optical materials, electrode materials and other applications.

Method used

Acid composites containing metals such as tungsten, tantalum, molybdenum, molybdenum and titanium are used to ensure that the particle diameter is 1000 nm or less through dynamic light scattering measurement, and alkali metals, phosphates or chlorides are added to improve solubility and stability.

Benefits of technology

These metallic acid composites are achieved with high soluble, stable and uniform film formation in polar solvents, and are suitable for the production of nonlinear optical materials and electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039502000001
    Figure 2025039502000001
  • Figure 2025039502000002
    Figure 2025039502000002
  • Figure 2025039502000003
    Figure 2025039502000003
Patent Text Reader

Abstract

To provide a metal acid compound dispersion with excellent water dispersibility, solubility, and storage stability, and a method for producing the same.SOLUTION: A metal acid compound dispersion contains at least two metals M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium, the metal acid compound dispersion containing: at least one element X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements; and a phosphorus compound and / or a chlorine compound. The particle diameter (D50) of the particles in the metal acid compound dispersion is at most 1000 nm as determined by the dynamic light scattering method.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal acid compound dispersion and a method for producing the same. [Background technology]

[0002] Metal oxide lithium, which is a composite of a metal element such as niobium, tantalum, molybdenum, or tungsten and lithium, an alkali metal element, is used in nonlinear optical materials, piezoelectric elements, battery materials, and the like. For example, in composite active material particles capable of reducing the battery resistance generated in an all-solid-state lithium-ion battery, a lithium metal oxide is cited as a lithium ion conductive oxide that covers at least a part of the surface of the composite active material particles. In addition, for example, Patent Document 1 discloses a piezoelectric sensor in which a piezoelectric film layer containing lithium niobate powder is formed on a substrate layer of the piezoelectric sensor. The piezoelectric sensor disclosed in Patent Document 1 is a piezoelectric film layer formed by spraying a mixture of lithium niobate powder and a sol-gel solution and then sintering the mixture. In addition, the tantalum oxide sol disclosed in Patent Document 2, specifically lithium tantalate, has excellent optical properties, nonlinear properties, and electro-optical properties, and is used in piezoelectric elements, and the like. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2023-63187 A [Patent Document 2] Japanese Patent Application Publication No. 8-143315 Summary of the Invention [Problem to be solved by the invention]

[0004] However, in the piezoelectric sensor disclosed in Patent Document 1, when the mixture of lithium niobate powder and sol-gel solution is spray-coated, if the lithium niobate powder has low dispersibility or solubility in the solvent, it is difficult to form a uniform piezoelectric film layer. In addition, if the mixture of lithium niobate powder and solvent has poor storage stability, the spray coating operation becomes complicated. Furthermore, since the tantalum oxide sol disclosed in Patent Document 2 contains an organic component such as oxalic acid that is difficult to volatilize, the organic component may be a factor that hinders the formation of a uniform film, and may be a factor that inhibits the catalytic action when used as an additive for a catalyst. In addition, lithium tantalate has poor dispersibility and solubility in water compared to lithium niobate, is prone to precipitates due to changes over time, and does not have excellent storage stability.

[0005] In view of the above problems, the present invention provides a metal acid compound dispersion liquid that has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability, and a method for producing the same. [Means for solving the problem]

[0006] The metal acid compound dispersion of the present invention, which has been made to solve the above-mentioned problems, is a metal acid compound dispersion containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten and titanium, and containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound, and is characterized in that the particle diameter (D50) of particles in the metal acid compound dispersion measured by dynamic light scattering method is 1000 nm or less. The metal acid compound dispersion of the present invention contains two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten and titanium, one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or the chlorine compound. If the particle size (D50) of the particles in the tantalic acid compound dispersion measured by dynamic light scattering method is 1000 nm or less, this is preferred in terms of improving the dispersibility and solubility in polar solvents, particularly water.

[0007] The metal acid compound dispersion of the present invention contains two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium. The metal species M is considered to be present as an oxide in the metal acid compound dispersion of the present invention. Specifically, niobium is NbO3 - Tantalum is thought to exist as an anion such as TaO3 or as a polyoxometalate (polyacid) ion in which multiple niobium atoms are bonded to oxygen atoms. - It is believed that molybdenum exists as an anion such as MoO4 or as a polyoxometalate (polyacid) ion in which multiple tantalum atoms are bonded to oxygen atoms. 2- It is believed that tungsten exists as an anion such as (W2O7) or as a polyoxometalate (polyacid) ion in which multiple molybdenum atoms are bonded to oxygen atoms. 2- Or, (W 12 O 10 ) 8- It is believed that titanium exists as an anion such as (Ti3O7) or as a polyoxometalate (polyacid) ion in which multiple tungsten atoms are bonded to oxygen atoms. 2- These are thought to exist as anions such as those shown below, or as polyoxometalate (polyacid) ions in which multiple titanium atoms are bonded to oxygen atoms.

[0008] Furthermore, it is preferable that the metal species M contains tantalum. Specifically, the metal species M may be two metal species, tantalum and one metal species selected from niobium, molybdenum, tungsten, or titanium, three metal species, tantalum and two metal species selected from niobium, molybdenum, tungsten, or titanium, four metal species, tantalum and three metal species selected from niobium, molybdenum, tungsten, or titanium, or may include all five metal species, tantalum, niobium, molybdenum, tungsten, and titanium. The metal species M may be two metal species selected from niobium, molybdenum, tungsten, or titanium excluding tantalum, three metal species selected from niobium, molybdenum, tungsten, or titanium, or four metal species selected from niobium, molybdenum, tungsten, and titanium.

[0009] The metal acid compound dispersion of the present invention contains one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements. That is, it is presumed that the metal acid in the metal acid compound dispersion of the present invention is present in the dispersion as an ion in an ionic state with an ion of one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements. It is considered that in the metal acid compound dispersion of the present invention, hydroxide ions are present as anions, while halide ions such as fluoride ions and chloride ions are hardly present, and alkali metal elements and alkaline earth metal elements are present as cations.

[0010] Furthermore, the element X preferably contains Li. Moreover, the element X is not limited to only one alkali metal element Li, but is preferably two alkali metal elements Li and Na or K, or three alkali metal elements Li, Na, and K. Furthermore, the element X may be one alkali metal element Na or K, or two alkali metal elements Na and K.

[0011] The metal acid compound dispersion of the present invention contains a phosphorus compound. In addition, in the metal acid compound dispersion of the present invention, the phosphorus compound may contain one or more compounds selected from inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

[0012] Examples of inorganic phosphorus compounds include inorganic phosphoric acids, particularly phosphoric acids, phosphonic acids, and phosphinic acids.Specific examples of phosphoric acids include phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), and polyphosphoric acid (CAS number: 8071-16-1).In addition, examples of phosphonic acids include phosphorous acid (CAS number: 13598-36-2) and hypophosphorous acid (CAS number: 6303-21-5).In addition, examples of phosphinic acids include phosphinic acid (CAS number: 6303-21-5).

[0013] In addition, examples of the organic phosphorus compound include phosphate esters, organic phosphites, organic phosphonic acids, and organic phosphines.Specific examples of the organic phosphorus compound include methyl phosphate (CAS number: 52932-95-3), ethyl phosphate (CAS number: 37203-76-2), butyl phosphate (CAS number: 107-66-4), phenyl phosphate (CAS number: 701-64-4), dimethyl phosphate (CAS number: 813-78-5), diethyl phosphate (CAS number: 598-02-7), dibutyl phosphate (CAS number: 107-66-4), diphenyl phosphate (CAS number: 838-85-7), trimethyl phosphate (CAS number: 512-56-1), triethyl phosphate (CAS number: 78-40-0), tributyl phosphate (CAS number: 126-73-8), and triphenyl phosphate (CAS number: 115-86-6).

[0014] In addition, organic phosphite acids and organic phosphonates include methylphosphonic acid (CAS number: 993-13-5), ethylphosphonic acid (CAS number: 6779-09-5), butylphosphonic acid (CAS number: 3321-64-0), phenylphosphonic acid (CAS number: 1571-33-1), dimethyl phosphite (dimethyl phosphonate) (CAS number: 868-85-9), diethyl phosphite (diethyl phosphonate) (CAS number : 762-04-9), dibutyl phosphite (dibutyl phosphonate) (CAS number: 1809-19-4), diphenyl phosphite (diphenyl phosphonate) (CAS number: 4712-55-4), trimethyl phosphite (CAS number: 121-45-9), triethyl phosphite (CAS number: 122-52-1), tributyl phosphite (CAS number: 102-85-2), and triphenyl phosphite (CAS number: 101-02-0).

[0015] Examples of the salts of inorganic phosphorus compounds and / or organic phosphorus compounds include ammonium salts of inorganic phosphorus compounds and / or organic phosphorus compounds, salts with organic nitrogen compounds, alkali metal salts, and alkaline earth metal salts.

[0016] An example of the organic phosphinic acids is triphenylphosphine (CAS number: 603-35-0).

[0017] Examples of inorganic ammonium phosphate salts, salts with organic nitrogen compounds, alkali metal salts, and alkaline earth metal salts include ammonium phosphate, monoammonium phosphate (CAS number: 7722-76-1), diammonium phosphate (CAS number: 7783-28-0), sodium metaphosphate (CAS number: 10361-03-2), potassium metaphosphate (CAS number: 7790-53-6), sodium hexametaphosphate (CAS number: 10124-56-8), potassium hexametaphosphate, sodium pyrophosphate (CAS number: 7722-88-5), potassium pyrophosphate (CAS number: 7320-34-5), sodium polyphosphate (CAS number: 68915-31-1), potassium polyphosphate, sodium tripolyphosphate (CAS number: 7758-29-4), potassium tripolyphosphate (CAS number: 13845-36-8), sodium ultrapolyphosphate, and potassium ultrapolyphosphate.

[0018] In addition, in the metal acid compound dispersion of the present invention, the phosphorus compound preferably contains one or more selected from phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), polyphosphoric acid (CAS number: 8071-16-1), phosphorous acid (CAS number: 13598-36-2), hypophosphorous acid (CAS number: 6303-21-5), ammonium phosphate, primary ammonium phosphate (CAS number: 7722-76-1), secondary ammonium phosphate (CAS number: 7783-28-0), ammonium pyrophosphate, and ammonium polyphosphate. A phosphoric acid salt is more preferable when adjusting a solution to a pH closer to neutral, whereas a phosphorus compound that is a condensed phosphoric acid, or a salt of a condensed phosphoric acid such as pyrophosphoric acid, polyphosphoric acid, or a condensed phosphoric acid is more preferable when adjusting a solution to a high pH.

[0019] In this specification, "phosphoric acid" refers to orthophosphoric acid and does not include phosphoric acids such as pyrophosphoric acid, polyphosphoric acid, and phosphorous acid. The phosphorus compound may form a compound with an alkali metal element or an alkaline earth metal element. For example, when the phosphorus compound contains a hydroxyl group (P-OH group), it has a structure in which some or all of the hydrogen atoms in the hydroxyl group are substituted with an alkali metal element or an alkaline earth metal element.

[0020] The metal acid compound dispersion of the present invention further contains a chlorine compound. Examples of chlorine compounds include hydrochloric acid (CAS number: 7647-01-0), hypochlorous acid (CAS number: 7790-92-3), chlorous acid (CAS number: 13898-47-0), chloric acid (CAS number: 7790-93-4), and perchloric acid (CAS number: 7601-90-3).

[0021] The chlorine compound may be a salt of the above-mentioned chlorine compound, for example, ammonium salt, amine salt, quaternary ammonium salt, lithium salt, and preferably ammonium salt or lithium salt.Specific examples include ammonium chloride (CAS number: 12125-02-9), ammonium perchlorate (CAS number: 7790-98-9), lithium chloride (CAS number: 7447-41-8), lithium perchlorate (CAS number: 7791-03-9), methylamine hydrochloride (CAS number: 593-51-1), and dimethylamine hydrochloride (CAS number: 506-59-2).

[0022] In addition, when the metal acid compound dispersion liquid of the present invention contains a chlorine compound, it is preferable not to contain a chlorine compound in cases where corrosion or elution of the substrate is a concern depending on the material or type of the substrate to which the metal acid compound dispersion liquid of the present invention is applied. For example, when the metal acid compound dispersion liquid of the present invention is used for a positive electrode for a lithium ion secondary battery described later or for coating a positive electrode material, it is preferable not to contain a chlorine compound.

[0023] Furthermore, when the particle diameter (D50) of the particles in the metal acid compound dispersion liquid is 1000nm or less by dynamic light scattering method, it is preferable from the viewpoint of high dispersibility, little change over time, stability, reactivity during reaction or compounding with other substances, and film uniformity during film formation. Moreover, the particle diameter (D50) is preferably smaller, more preferably 800nm ​​or less, even more preferably 600nm or less, particularly preferably 500nm or less, more particularly preferably 300nm or less, even more particularly preferably 200nm or less, even more particularly preferably 100nm or less, even more preferably 50nm or less, even more preferably 30nm or less, even more preferably 20nm or less, even more preferably 10nm or less, even more particularly preferably 8nm or less, even more particularly preferably 6nm or less, even more particularly preferably 4nm or less, even more particularly preferably 2nm or less, even more particularly preferably 1nm or less, even more particularly preferably 0.6nm or less, and most preferably more than 0. In this way, a liquid in which the particle diameter (D50) of particles in the metal acid compound dispersion of the present invention is 1000 nm or less as a result of measurement using dynamic light scattering is defined as the "metal acid compound dispersion" of the present invention.

[0024] Here, the dynamic light scattering method is a method in which a solution such as a suspension is irradiated with light such as a laser beam to measure the light scattering intensity from a group of particles undergoing Brownian motion, and the particle size and distribution are obtained from the temporal variation of the intensity. Specifically, the particle size distribution is evaluated in accordance with JIS Z 8828:2019 "Particle Size Analysis - Dynamic Light Scattering Method" using a Zeta Potential, Particle Size, and Molecular Weight Measurement System (Otsuka Electronics Co., Ltd.: ELSZ-2000). In addition, the solution to be measured is filtered through a filter with a pore size of 1 μm to remove dust and other particles in the solution just before the measurement. The particle size (D50) refers to the median diameter (D50), which is the particle size that indicates the 50% cumulative value of the cumulative distribution curve. Furthermore, in this specification, unless otherwise specified, "particle diameter (D50)" includes both "initial particle diameter D50" which indicates the particle diameter (D50) of particles in the metal acid compound dispersion liquid of the present invention whose liquid temperature is adjusted to 25°C immediately after production, and "aged particle diameter D50" which indicates the particle diameter (D50) of particles in the niobate compound dispersion liquid of the present invention after it has been left to stand for one month from the day the metal acid compound dispersion liquid of the present invention is produced in an incubator set at room temperature of 25°C.

[0025] The metal acid compound dispersion of the present invention is a metal acid compound dispersion containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten and titanium, and is characterized in that it contains one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound, and has a maximum transmittance of 70%T or more in a wavelength region of 400 nm to 760 nm. Here, the two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten and titanium, the one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and the phosphorus compound and / or chlorine compound in the metal acid compound dispersion of the present invention are as described above, and therefore detailed description thereof will be omitted.

[0026] The metal oxide compound dispersion of the present invention is preferably such that the maximum transmittance in the wavelength region of 400 nm to 760 nm is 70%T or more, because the degree of dispersion is high and the uniformity of the liquid components is excellent. The maximum transmittance in the wavelength region of 400 nm to 760 nm is more preferably 72%T or more, even more preferably 74%T or more, particularly preferably 76%T or more, even more preferably 78%T or more, even more particularly preferably 80%T or more, even more particularly preferably 85%T or more, even more preferably 90%T or more, even more preferably 95%T or more, even more particularly preferably 97%T or more, even more particularly preferably 98%T or more, even more particularly preferably 99%T or more, and most preferably 100%T.

[0027] Furthermore, the metal acid compound dispersion liquid of the present invention may have a transmittance of 70%T or more at any one wavelength of 400 nm, 600 nm, or 750 nm. The transmittance at any one wavelength of 400 nm, 600 nm, or 750 nm, or any two or more wavelengths, may be 72%T or more, 74%T or more, 76%T or more, 78%T or more, 80%T or more, 85%T or more, 90%T or more, 95%T or more, 97%T or more, 98%T or more, 99%T or more, or 100%T or more.

[0028] Furthermore, the metal acid compound dispersion liquid of the present invention may have a minimum transmittance in a wavelength region of 400 nm to 760 nm of 70% T or more. The minimum transmittance in the wavelength region of 400 nm to 760 nm may be 72% T or more, 74% T or more, 76% T or more, 78% T or more, 80% T or more, 85% T or more, 90% T or more, 95% T or more, 97% T or more, 98% T or more, 99% T or more, or 100% T or more.

[0029] In addition, due to measurement errors, etc., the measured value of the transmittance may exceed 100%T, but since the theoretical upper limit is 100%, when the measured value exceeds 100%T, it is considered to be 100%T. In this way, a liquid in which the maximum value of the transmittance in the wavelength region of 400 nm to 760 nm of the metal acid compound dispersion of the present invention is 70%T or more is defined as the "metal acid compound dispersion" of the present invention. Furthermore, unless otherwise specified, in this specification, the "transmittance" includes both the "initial transmittance" indicating the transmittance of the metal acid compound dispersion of the present invention adjusted to a liquid temperature of 25°C immediately after production, and the "temporary transmittance" indicating the transmittance of the metal acid compound dispersion of the present invention after being left to stand for one month from the day of production in an incubator set at room temperature of 25°C.

[0030] Here, the above-mentioned transmittance can be determined by measuring the ultraviolet-visible absorption spectrum (UV-Vis absorption spectrum) of the metal acid compound dispersion of the present invention in accordance with the following transmittance measurement conditions in accordance with JIS K 0115, 2004 "General rules for spectrophotometric analysis methods".

[0031] =Transmittance measurement conditions= Measurement equipment: UV-Vis-NIR spectrophotometer UH4150 (manufactured by Hitachi High-Tech Science Corporation) Measurement mode: Wavelength scan Data mode: %T (transparent) Measurement wavelength range: 200nm~2000nm Scan speed: 600nm / min Sampling interval: 2nm

[0032] In the present invention, the "dispersion" is not limited to a dispersion in which a solute is dispersed or mixed in a solvent in a monomolecular state, but also includes an aggregate in which a plurality of molecules are attracted to each other by intermolecular interactions, such as (1) polymer molecules, (2) solvated molecules, (3) molecular clusters, and (4) colloidal particles dispersed in a solvent.

[0033] The metal acid compound dispersion of the present invention may further contain hydrogen peroxide. The metal acid compound dispersion liquid of the present invention may contain hydrogen peroxide since, in the method for producing a tantalic acid compound dispersion liquid, which will be described later, a tantalum compound aqueous solution can be produced by adding hydrogen peroxide to a tantalum fluoride aqueous solution and mixing them.

[0034] The method for detecting hydrogen peroxide in a metal acid compound dispersion of the present invention can be performed, for example, by using a standard addition method to measure the relative intensity of absorbance with a standard solution of hydrogen peroxide, thereby confirming the hydrogen peroxide content in the dispersion. Specifically, a wavelength region in which a change in absorbance due to the formation of a peroxo complex is observed is found from the UV-visible absorption spectrum of a standard solution containing a known content, for example, 1 mass% hydrogen peroxide, and a standard solution to which hydrogen peroxide is not added, and if the difference in absorbance between the standard solution to which hydrogen peroxide is not added and a sample to which the hydrogen peroxide content is unknown in that wavelength region is less than 1%, it can be confirmed that the sample to which the hydrogen peroxide content is unknown does not substantially contain hydrogen peroxide. When hydrogen peroxide is contained in the dispersion, hydrogen peroxide reacts with, for example, a polyacid of tantalum to form a peroxo complex, and therefore, by confirming the difference in absorbance with the standard solution to which hydrogen peroxide is not added as described above, it can be confirmed that hydrogen peroxide is not contained in the dispersion. In addition to the above-mentioned standard addition method, hydrogen peroxide in the dispersion may be qualitatively and quantitatively analyzed by, for example, using a commercially available hydrogen peroxide measurement kit, adding a reagent that undergoes a color reaction with hydrogen peroxide to the dispersion and measuring the color development, or by adding a reagent that undergoes a fluorescent reaction with hydrogen peroxide to the dispersion and measuring the light emission.

[0035] The metal acid compound dispersion of the present invention may further contain ammonia and / or an organic nitrogen compound. The metal acid compound dispersion of the present invention may contain an ionized alkaline aqueous solution, such as ammonia or an organic nitrogen compound. The content of ammonia or an organic nitrogen compound in the metal acid compound dispersion of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, and particularly preferably 1% by mass or less, when the metal acid compound dispersion of the present invention is taken as 100% by mass.

[0036] As will be described in detail in the method for producing a metal acid compound dispersion of the present invention later, for example, in the method for producing a tantalic acid compound dispersion, a reverse neutralization method is used in which an acidic tantalum complex aqueous solution is added to an alkaline aqueous solution, for example, ammonia water, to produce a tantalic acid-containing precipitate, which is a tantalum-containing precipitate slurry, for example, ammonium tantalate hydrous cake, and then a tantalic acid compound dispersion is produced, so it is considered that ammonia contains ammonium ions and exists in the dispersion as cations. Also, in the method for producing a tantalic acid compound dispersion, a reverse neutralization method is used in which an acidic tantalum complex aqueous solution is added to an alkaline aqueous solution, for example, ammonia water, and the tantalic acid compound dispersion is produced by mixing the tantalic acid-containing precipitate obtained through the reverse neutralization method in which the tantalic acid complex is added to ammonia water with an organic nitrogen compound, so that the organic nitrogen compound exists in the dispersion as cations.

[0037] The method for measuring the ammonia content in the dispersion liquid includes a method of adding sodium hydroxide to the dispersion liquid to separate the ammonia by distillation and quantifying the ammonia content with an ion meter, a method of quantifying the N content in a gasified sample with a thermal conductivity meter, the Kjeldahl method, gas chromatography (GC), ion chromatography, gas chromatography mass spectrometry (GC-MS), etc. In particular, the method of quantifying the ammonia content with an ion meter is preferred.

[0038] Examples of the organic nitrogen compounds include aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium compounds, guanidine compounds, and azole compounds.

[0039] Examples of aliphatic amines include methylamine, dimethylamine, trimethylamine, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, tert-butylamine, n-pentamine, n-hexylamine, cyclohexylamine, piperidine, and the like.

[0040] Examples of aromatic amines include aniline, phenylenediamine, and diaminotoluene. Examples of amino alcohols include methanolamine, ethanolamine, propanolamine, butanolamine, pentanolamine, dimethanolamine, diethanolamine, trimethanolamine, methylmethanolamine, methylethanolamine, methylpropanolamine, methylbutanolamine, ethylmethanolamine, ethylethanolamine, ethylpropanolamine, dimethylmethanolamine, dimethylethanolamine, dimethylpropanolamine, methyldimethanolamine, methyldiethanolamine, diethylmethanolamine, trishydroxymethylaminomethane, bis(2-hydroxyethyl)aminotris(hydroxymethyl)methane, and aminophenol. Examples of amino acids include alanine, arginine, aspartic acid, and EDTA. Examples of polyamines include polyamines and polyetheramines.

[0041] Examples of quaternary ammonium include alkylimidazolium, pyridinium, pyrrolidium, tetraalkylammonium, etc. Specific examples of alkylimidazolium include 1-methyl-3-methylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1-methyl-2,3-dimethylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-propyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, etc. Specific examples of pyridinium and pyrrolidium include N-butyl-pyridinium, N-ethyl-3-methyl-pyridinium, N-butyl-3-methyl-pyridinium, N-hexyl-4-(dimethylamino)-pyridinium, N-methyl-1-methylpyrrolidinium, and N-butyl-1-methylpyrrolidinium. Specific examples of tetraalkylammonium include tetramethylammonium, tetraethylammonium, tetrabutylammonium, and ethyl-dimethyl-propylammonium. Examples of anions that form salts with the above-mentioned cations include OH, - , Cl - , Br - , I - , BF4 - , HSO4 - etc.

[0042] Examples of the guanidine compound include guanidine, diphenylguanidine, and ditolylguanidine. Examples of the azole compound include imidazole compounds and triazole compounds. Specific examples of the imidazole compound include imidazole, 2-methylimidazole, and 2-ethyl-4-methylimidazole. Specific examples of the triazole compound include 1,2,4-triazole, 1,2,4-triazole-3-methyl carboxylate, and 1,2,3-benzotriazole.

[0043] Here, the organic nitrogen compound is preferably an aliphatic amine because it is highly volatile and has low toxicity. Specifically, an aliphatic amine having 1 to 4 carbon atoms is more preferable, and an aliphatic amine having 1 to 2 carbon atoms is particularly preferable. Examples of the organic nitrogen compound include methylamine and dimethylamine.

[0044] In addition, the organic nitrogen compound is preferably a quaternary ammonium, since it has high solubility and high crystallization inhibition and high sol formation inhibition. For example, tetraalkylammonium salts are preferred, tetraalkylammonium hydroxide salts are more preferred, tetramethylammonium hydroxide and tetraethylammonium are particularly preferred, and tetramethylammonium hydroxide (TMAH) is also particularly preferred.

[0045] Furthermore, the organic nitrogen compound may be a mixture of two or more selected from aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium, guanidine compounds, and azole compounds, rather than one selected from them. For example, a mixture of two types of compounds, an aliphatic amine and a quaternary ammonium compound, is preferable in that the amount of the compound added is reduced so as not to increase toxicity, while the solubility can be increased.

[0046] Specifically, examples of such mixtures include mixtures of two organic nitrogen compounds, such as methylamine and tetramethylammonium hydroxide (TMAH), dimethylamine and tetramethylammonium hydroxide (TMAH), and methylamine and dimethylamine, and mixtures of three organic nitrogen compounds, such as methylamine, dimethylamine, and tetramethylammonium hydroxide (TMAH).

[0047] The method for measuring the content of the organic nitrogen compound present in the metal acid compound dispersion of the present invention includes gas chromatography (GC), liquid chromatography (LC), mass spectrometry (MS), gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), etc. When a low-volatility organic nitrogen compound is contained, it is preferable to measure the content of the organic nitrogen compound by liquid chromatography (LC) or liquid chromatography-mass spectrometry (LC-MS).

[0048] The metal acid compound dispersion of the present invention is characterized in that the content of the metal species M in the metal acid compound dispersion is 0.01% by mass or more and 30% by mass or less in terms of the metal species M atom. The content of the metal species M in the metal acid compound dispersion of the present invention is preferably from 0.01% by mass to 30% by mass, calculated as the metal species M atom, in terms of achieving both practicality and stability of the metal acid compound dispersion, and is more preferably from 0.5% by mass to 25% by mass, calculated as the metal species M atom, even more preferably from 1% by mass to 20% by mass, calculated as the metal species M atom, particularly preferably from 1% by mass to 15% by mass, even more particularly preferably from 3% by mass to 10% by mass, and even more particularly preferably from 5% by mass to 10% by mass, calculated as the metal species M atom.

[0049] The content of the metal species M can be determined as follows.

[0050] When the metal species M contained in the metal acid compound dispersion of the present invention is two types, tantalum and niobium, the sum of the tantalum content in terms of Ta atoms and the niobium content in terms of Nb atoms in the metal acid compound dispersion of the present invention is the content of the metal species M in the metal acid compound dispersion of the present invention.

[0051] Furthermore, when the metal species M contained in the metal acid compound dispersion liquid of the present invention is the three types of tantalum, niobium, and molybdenum, the sum of the tantalum content in terms of Ta atoms, the niobium content in terms of Nb atoms, and the molybdenum content in terms of Mo atoms in the metal acid compound dispersion liquid of the present invention is the content of the metal species M in the metal acid compound dispersion liquid of the present invention.

[0052] Furthermore, when the metal species M contained in the metal acid compound dispersion liquid of the present invention is one of the four types, namely tantalum, molybdenum, tungsten, and titanium, the sum of the tantalum content in terms of Ta atoms, the molybdenum content in terms of Mo atoms, the tungsten content in terms of W atoms, and the titanium content in terms of Ti atoms in the metal acid compound dispersion liquid of the present invention is the content of the metal species M in the metal acid compound dispersion liquid of the present invention.

[0053] Furthermore, when the metal species M contained in the metal acid compound dispersion liquid of the present invention is one of the five types, namely tantalum, niobium, molybdenum, tungsten, and titanium, the sum of the tantalum content in terms of Ta atoms, the niobium content in terms of Nb atoms, the molybdenum content in terms of Mo atoms, the tungsten content in terms of W atoms, and the titanium content in terms of Ti atoms in the metal acid compound dispersion liquid of the present invention is the content of the metal species M in the metal acid compound dispersion liquid of the present invention.

[0054] Here, the metal species M content in the metal acid compound dispersion is calculated by diluting the dispersion appropriately with dilute hydrochloric acid as necessary, and measuring Nb mass% in terms of Nb atoms, Ta mass% in terms of Ta atoms, Mo mass% in terms of Mo atoms, W mass% in terms of W atoms, and Ti mass% in terms of Ti atoms, in accordance with JIS K0116:2014, using high-frequency inductively coupled plasma optical emission spectroscopy (ICP optical emission spectroscopy (AG-5110 manufactured by Agilent Technologies, Inc.)). In addition, when the metal acid in the metal acid compound dispersion of the present invention is ionically bonded with an alkali metal or an alkaline earth metal, for example, a lithium metal acid salt ionically bonded with a lithium ion, the lithium content may be calculated by measuring Li mass% in terms of Li atoms, as in the case of the metal species M content. By specifying the metal species M content and lithium content in the metal acid compound dispersion of the present invention, the molar ratio Li / m of lithium (Li) and metal species M (m) of the lithium metal acid lithium contained in the metal acid compound dispersion of the present invention can be specified. The content of each element X of one or more elements X selected from the group consisting of alkali metal elements other than lithium and / or alkaline earth metal elements can be calculated by measuring the mass % of each element X in terms of element X atoms in the same manner as the content of the metal species M.

[0055] The metal acid compound dispersion liquid of the present invention is characterized in that the phosphorus content in the metal acid compound dispersion liquid is 0.01% by mass or more and 10% by mass or less in terms of P atoms. The phosphorus content in the metal oxide compound dispersion of the present invention is preferably 0.01% by mass or more and 10% by mass or less in terms of P atoms, since dispersibility and solubility in polar solvents, particularly water, is improved. Also, the phosphorus content is more preferably 0.01% by mass or more and 5% by mass or less in terms of P atoms, further preferably 0.05% by mass or more and 2% by mass or less in terms of P atoms, and particularly preferably 0.05% by mass or more and 1% by mass or less in terms of P atoms.

[0056] The phosphorus content in the metal acid compound dispersion of the present invention is calculated by diluting the dispersion appropriately with dilute hydrochloric acid as necessary, and measuring the P mass% in terms of P atoms using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.

[0057] The phosphorus content in the metal oxide compound dispersion of the present invention is preferably analyzed by the above-mentioned ICP emission spectrometry. 31 It can also be determined by measuring the P-NMR spectrum. Specifically, the phosphorus content in the metal acid compound dispersion of the present invention can be determined by the following procedure using a nuclear magnetic resonance apparatus (AVANCE NEO 600 manufactured by Bruker). A measurement sample is prepared by mixing 70 μL of the metal acid compound dispersion of the present invention with 650 μL of a phosphonoacetic acid deuterium oxide solution prepared by dissolving 10 g / L of phosphonoacetic acid in deuterium oxide. The prepared measurement sample is subjected to the following measurement. 31 According to the P-NMR spectrum measurement conditions, 31 Measure the P-NMR spectrum.

[0058] = 31 P-NMR spectrum measurement conditions: ·Magnetic field: 14.1 T (1H 600Mhz) Spectrometer: Bruker AVANCE NEO 600 Measurement and data processing software: Bruker, TopSpin NMR probe: Solvent probe (Type: PA BBO 600S3 BBF-HD-05 Z SP) Solvent: Deuterium oxide Chemical shift values ​​and phosphorus content of internal sample: phosphonoacetic acid Chemical shift value standard: The apex of the central peak of the triplet peak of phosphonoacetic acid is set to 14.96 ppm. Spectral center (O1 value - SR value (chemical shift value)): 0.00 ppm Radio frequency pulse intensity: The intensity at which a 14μs pulse is at 90 degrees to the peak at the center of irradiation. Radio frequency pulse width: 14μs Measurement interval: 80μs (DW=40μs on the software) Number of measurement points: 32768 points (TD=65536 on the software) Number of spectrum points (SI on the software): 65536 points

[0059] As mentioned above 31 By performing a Fourier transform on the FID data measured under the P-NMR spectrum measurement conditions without using a window function, 31 The P-NMR spectrum was obtained. 31 The peak areas of the P-NMR spectrum can be calculated using the Integrate function of the above-mentioned measurement and data processing software, and the contents of phosphonoacetic acid and each phosphate ion can be calculated from the peak areas. For example, in the diphosphate raw material, the peak areas are 6.5 ppm (estimated to be derived from PO4 based on the chemical shift value) and -1.7 ppm (estimated to be derived from P2O7 based on the chemical shift value), 31 P peak is observed. In phosphoric acid raw material, it is 6.2 ppm (estimated to be derived from PO4), 31 The P peak is observed. The chemical shifts of each peak are affected by factors such as the pH of the sample, so calculations must be made taking this into account.

[0060] Furthermore, the metal acid compound dispersion of the present invention preferably has a chlorine content of 0.0% by mass or more and 2.0% by mass or less in terms of Cl atoms. The chlorine content in the metal oxide compound dispersion of the present invention is preferably 0.0% by mass or more and 2.0% by mass or less in terms of Cl atoms in terms of the risk of corrosion to the substrate, more preferably 0.001% by mass or more and 2.0% by mass or less in terms of Cl atoms, even more preferably 0.001% by mass or more and 0.5% by mass or less in terms of Cl atoms, particularly preferably 0.001% by mass or more and 0.2% by mass or less in terms of Cl atoms, and even more particularly preferably 0.001% by mass or more and 0.1% by mass or less in terms of Cl atoms.

[0061] The chlorine content in the metal acid compound dispersion of the present invention is calculated by diluting the dispersion appropriately with dilute hydrochloric acid as necessary, and measuring the Cl mass% in terms of Cl atoms using ICP emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116: 2014. In this case, the chlorine content in the metal acid compound dispersion of the present invention can be calculated by subtracting the chlorine content derived from the dilute hydrochloric acid used for dilution.

[0062] Furthermore, in the metal acid compound dispersion of the present invention, the total content of the phosphorus content calculated as P atoms and the chlorine content calculated as Cl atoms in the metal acid compound dispersion is preferably from 0.01% by mass to 10% by mass. The total content in the metal acid compound dispersion of the present invention is preferably 0.01% by mass or more and 10% by mass or less in terms of improving dispersibility and solubility in polar solvents, particularly water, and more preferably 0.01% by mass or more and 5% by mass or less, even more preferably 0.05% by mass or more and 2% by mass or less, and particularly preferably 0.05% by mass or more and 1% by mass or less.

[0063] The metal acid compound dispersion of the present invention is characterized in that the molar ratio x / m of the total amount (x) of the element X to the total amount (m) of the metal species M in the metal acid compound dispersion is 0.01 or more and 10 or less. The molar ratio x / m of the total amount (x) of the element X to the total amount (m) of the metal species M in the metal acid compound dispersion of the present invention is preferably from 0.01 to 10 in terms of improving dispersibility and solubility in water, more preferably from 0.05 to 9, even more preferably from 0.1 to 8, and particularly preferably from 1 to 7. The molar ratio x / m of the total amount (x) of the element X to the total amount (m) of the metal species M in the metal acid compound dispersion of the present invention may be from 0.1 to 9, or may be from 0.1 to 7.

[0064] The total amount (m) of the metal species M can be determined as follows.

[0065] When the metal species M contained in the metal acid compound dispersion of the present invention is two types, tantalum and niobium, the sum of the number of moles of tantalum and the number of moles of niobium per 1 L of the metal acid compound dispersion of the present invention is the total amount (m) of the metal species M in the metal acid compound dispersion of the present invention.

[0066] Furthermore, when the metal species M contained in the metal acid compound dispersion of the present invention is the three types, namely tantalum, niobium, and molybdenum, the sum of the number of moles of tantalum, the number of moles of niobium, and the number of moles of molybdenum per 1 L of the metal acid compound dispersion of the present invention is the total amount (m) of the metal species M in the metal acid compound dispersion of the present invention.

[0067] Furthermore, when the metal species M contained in the metal acid compound dispersion of the present invention is the four types, namely tantalum, molybdenum, tungsten, and titanium, the sum of the number of moles of tantalum, the number of moles of molybdenum, the number of moles of tungsten, and the number of moles of titanium per 1 L of the metal acid compound dispersion of the present invention is the total amount (m) of the metal species M in the metal acid compound dispersion of the present invention.

[0068] Furthermore, when the metal species M contained in the metal acid compound dispersion of the present invention is five types, namely tantalum, niobium, molybdenum, tungsten, and titanium, the sum of the number of moles of tantalum, the number of moles of niobium, the number of moles of molybdenum, the number of moles of tungsten, and the number of moles of titanium per 1 L of the metal acid compound dispersion of the present invention is the total amount (m) of the metal species M in the metal acid compound dispersion of the present invention.

[0069] The metal acid compound dispersion of the present invention is characterized in that the element X in the metal acid compound dispersion is Li, and the molar ratio Li / m of lithium (Li) to the total amount (m) of the metal species M is 0.01 or more and 10 or less. When the element X in the metal acid compound dispersion of the present invention is Li, the molar ratio Li / m of lithium (Li) to the total amount (m) of the metal species M is preferably 0.01 or more and 10 or less in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 9 or less, even more preferably 0.1 or more and 8 or less, and particularly preferably 1 or more and 7 or less. Note that when the element X in the metal acid compound dispersion of the present invention is Li, the molar ratio Li / m of lithium (Li) to the total amount (m) of the metal species M may be 0.1 or more and 9 or less, or 0.1 or more and 7 or less.

[0070] The metal acid compound dispersion of the present invention is characterized in that the molar ratio x / (P+Cl) of the total amount (x) of the element X to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound in the metal acid compound dispersion is 0.01 or more and 5 or less. The molar ratio x / (P+Cl) of the total amount (x) of the element X to the total amount (P+Cl) of the phosphorus compound and / or chlorine compound in the metal acid compound dispersion of the present invention is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2, even more preferably 0.05 to 2, and particularly preferably 0.1 to 1.95. In this specification, unless otherwise specified, the total amount (P+Cl) of the phosphorus compound and / or chlorine compound is the sum of the value (P) calculated in terms of P atoms and the value (Cl) calculated in terms of Cl atoms. In addition, when the metal acid compound dispersion of the present invention is used for a lithium ion secondary battery positive electrode or a coating for a positive electrode material described later, the total amount (P+Cl) of the phosphorus compound and / or chlorine compound is preferably Cl=0.

[0071] Furthermore, in the metal acid compound dispersion of the present invention, the molar ratio x / P of the total amount (x) of the element X to the total amount (P) of the phosphorus compound in the metal acid compound dispersion is more preferably 0.01 or more and 5 or less. The molar ratio x / P of the total amount (x) of the element X to the total amount (P) of the phosphorus compounds in the metal acid compound dispersion of the present invention is preferably from 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably from 0.01 to 2, even more preferably from 0.05 to 2, and particularly preferably from 0.1 to 1.95.

[0072] The metal acid compound dispersion of the present invention is characterized in that the molar ratio x / (P+Cl) of the total amount (x) of the element X to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound in the metal acid compound dispersion is 0.01 or more and 5 or less. The molar ratio x / (P+Cl) of the total amount (x) of the element X to the total amount (P+Cl) of the phosphorus compounds and / or chlorine compounds in the metal acid compound dispersion of the present invention is preferably from 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably from 0.01 to 2, even more preferably from 0.05 to 2, and particularly preferably from 0.1 to 1.95.

[0073] In the metal acid compound dispersion of the present invention, the molar ratio x / P of the total amount (x) of the element X to the total amount (P) of the phosphorus compound in the metal acid compound dispersion is more preferably 0.01 or more and 5 or less. The molar ratio x / P of the total amount (x) of the element X to the total amount (P) of the phosphorus compounds in the metal acid compound dispersion of the present invention is preferably from 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably from 0.01 to 2, even more preferably from 0.05 to 2, and particularly preferably from 0.1 to 1.95.

[0074] The metal acid compound dispersion of the present invention is characterized in that the element X in the metal acid compound dispersion is Li, and the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is 0.01 or more and 5 or less. When the element X in the metal acid compound dispersion liquid of the present invention is Li, the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is preferably 0.01 or more and 5 or less in terms of improving dispersibility and solubility in water, more preferably 0.01 or more and 2 or less, even more preferably 0.05 or more and 2 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0075] Furthermore, in the metal acid compound dispersion of the present invention, it is more preferable that the element X in the metal acid compound dispersion is Li, and the molar ratio Li / P of lithium (Li) to the total amount (P) of the phosphorus compounds is 0.01 or more and 5 or less. When the element X in the metal acid compound dispersion liquid of the present invention is Li, the molar ratio Li / P of lithium (Li) to the total amount (P) of the phosphorus compound is preferably 0.01 or more and 5 or less in terms of improving dispersibility and solubility in water, more preferably 0.01 or more and 2 or less, even more preferably 0.05 or more and 2 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0076] The metal acid compound dispersion of the present invention is also characterized in that the molar ratio m / (P+Cl) of the total amount (m) of the metal species M to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is 0.01 or more and 10 or less. The molar ratio m / (P+Cl) of the total amount (m) of the metal species M to the total amount (P+Cl) of the phosphorus compounds and / or chlorine compounds in the metal acid compound dispersion of the present invention is preferably 0.01 or more and 10 or less in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0077] Furthermore, in the metal acid compound dispersion of the present invention, it is more preferable that the molar ratio m / P of the total amount (m) of the metal species M to the total amount (P) of the phosphorus compound is 0.01 or more and 10 or less. The molar ratio m / P of the total amount (m) of the metal species M to the total amount (P) of the phosphorus compounds in the metal acid compound dispersion of the present invention is preferably 0.01 or more and 10 or less in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0078] Furthermore, in the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Nb, the molar ratio Nb / (P+Cl) of niobium (Nb) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0079] Furthermore, in the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Nb, the molar ratio Nb / P of niobium (Nb) to the total amount (P) of the phosphorus compounds is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0080] In the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Ta, the molar ratio Ta / (P+Cl) of tantalum (Ta) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0081] In the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Ta, the molar ratio Ta / P of tantalum (Ta) to the total amount (P) of the phosphorus compound is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0082] In the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Mo, the molar ratio Mo / (P+Cl) of molybdenum (Mo) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0083] Furthermore, in the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Mo, the molar ratio Mo / P of molybdenum (Mo) to the total amount (P) of the phosphorus compounds is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0084] In the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is W, the molar ratio W / (P+Cl) of tungsten (W) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0085] Furthermore, in the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is W, the molar ratio W / P of tungsten (W) to the total amount (P) of the phosphorus compound is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0086] In the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Ti, the molar ratio Ti / (P+Cl) of titanium (Ti) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0087] In the metal acid compound dispersion of the present invention, when the metal species M in the metal acid compound dispersion is Ti, the molar ratio Ti / P of titanium (Ti) to the total amount (P) of the phosphorus compounds is preferably 0.01 or more and 10 or less, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0088] The metal oxide compound dispersion of the present invention is characterized in that it is an aqueous dispersion. The metal acid compound in the metal acid compound dispersion of the present invention has high dispersibility in water and good solubility in water, so pure water can be used as the solvent. An organic solvent may be used as the solvent. Examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, etc., and the solvent may be a mixture of these organic solvents and pure water. Examples of the alcohol solvent include alcohols having 5 or less carbon atoms (methanol, ethanol, n-propanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol), high boiling point solvents, acetone, etc. It is preferable that the above-mentioned solvents and water are compatible with each other. The metal acid compound dispersion of the present invention may contain one or more solvents at any ratio within a range that does not impair stability.

[0089] Examples of high boiling point solvents include polyhydric alcohol solvents and glycol solvents. Examples of polyhydric alcohol solvents include glycerin (boiling point: 290°C), 1,6-hexanediol (boiling point: 250°C), and 1,7-heptanediol (boiling point: 259°C). Examples of glycol solvents include ethylene glycol (boiling point: 197.3°C), propylene glycol (boiling point: 188.2°C), diethylene glycol (boiling point: 244.3°C), triethylene glycol (boiling point: 287.4°C), oligoethylene glycol (boiling point: 287°C to 460°C), polyethylene glycol (PEG) (boiling point: 460°C or higher), polyethylene glycol (PEG)-polypropylene glycol (PPG) copolymer (boiling point: 460°C). or higher), diethylene glycol monohexyl ether (boiling point: 260°C), polyoxyalkylene monoalkyl ether (boiling point: 260°C or higher), polyoxyethylene sorbitan monolaurate (boiling point: 321°C or higher), other anionic fluorosurfactants (boiling point: 180°C or higher), amphoteric fluorosurfactants (boiling point: 180°C or higher), nonionic fluorosurfactants (boiling point: 180°C or higher), amine oxides (boiling point: 180°C or higher), etc. The above boiling points are those at 1 atmospheric pressure.

[0090] The metal acid compound dispersion of the present invention is characterized in that the metal acid compound dispersion has a pH of 2 or more and 11 or less. The pH of the metal acid compound dispersion of the present invention is preferably 2 or more and 11 or less, since the polyacid ions contained in the dispersion are stable. In addition, as for the metal acid compound dispersion of the present invention, an acidic metal acid compound dispersion may be preferable, a neutral metal acid compound dispersion may be preferable, or a basic metal acid compound dispersion may be preferable depending on the application. In this specification, unless otherwise specified, "pH" refers to both "initial pH", which is the pH of the metal acid compound dispersion of the present invention adjusted to a liquid temperature of 25°C immediately after production, and "pH over time", which is the pH of the metal acid compound dispersion of the present invention after being left to stand for one month from the day the metal acid compound dispersion of the present invention was produced in an incubator set at room temperature of 25°C.

[0091] When an acidic metal acid compound dispersion is preferred, the pH of the metal acid compound dispersion of the present invention is preferably less than 7, and more preferably pH 2 or more and less than 7. When a neutral metal acid compound dispersion is preferred, the pH of the metal acid compound dispersion of the present invention is preferably 6 or more and 8 or less, and more preferably pH 7. When a basic metal acid compound dispersion is preferred, the pH of the metal acid compound dispersion of the present invention is preferably 7 or more, more preferably pH 8 or more, even more preferably pH 9 or more, and particularly preferably pH 10 or more. On the other hand, the pH is preferably 11 or less. Furthermore, the pH may be 11 or more, or may be 12 or more. In addition, when an organic acid is contained in the metal acid compound dispersion of the present invention, the pH is changed, and the components in the metal acid compound dispersion of the present invention may interact with the organic acid, so it is preferable that no organic acid is contained.

[0092] Here, the pH of the metal acid compound dispersion of the present invention is measured by immersing an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) in the metal acid compound dispersion of the present invention and confirming that the liquid temperature has stabilized at 25°C.

[0093] The metal acid compound dispersion of the present invention may contain an element or a compound thereof that does not constitute the metal acid compound contained in the metal acid compound dispersion of the present invention as an additive. Examples of the additive include elements or compounds such as Al, Si, V, Mn, Fe, Co, Ni, Cu, Zn, Ge, Zr, Sn, and La. Examples of the compound include oxides, alkali metal salts of metal acids, alkaline earth metal salts of metal acids, chlorides, alkoxides of metal acids, and polyoxometalates. In addition, the content of the additive in the metal acid compound dispersion of the present invention is, when the total molar content of each element as an additive is Z, the molar ratio Z / m of the total molar content (Z) of each element as an additive to the total amount (m) of the metal species M may be 0.001 to 75, 0.002 to 50, 0.01 to 40, 0.2 to 30, 0.5 to 25, 0.8 to 1.5, 0.8 to 1.3, 0.9 to 1.2, or 0.9 to 1.1. The content of each element corresponding to the additive is calculated by measuring the mass% of each element in terms of the atomic content of each element, similarly to the content of the metal species M described above. Furthermore, since the metal acid compound dispersion of the present invention is a uniform dispersion, even if these compounds are in a suspended state, improvement in uniformity and improvement in reactivity (reaction rate) are expected. In addition, if these compounds are dissolved in the metal acid compound dispersion of the present invention and become a uniform dispersion, the composite element can be in the most reactive state.

[0094] Furthermore, the metal acid compound dispersion of the present invention may contain components (referred to as "other components") other than the components derived from metals or metal acids, ammonia, organic nitrogen compounds, and the components derived from element X, within a range that does not impair the action and effect of the metal acid compound dispersion. Examples of the other components include Al, Si, V, Mn, Fe, Co, Ni, Cu, Zn, Ge, Zr, Sn, La, etc. However, the other components are not limited to these. When the metal acid compound dispersion of the present invention is taken as 100 mass%, the content of the other components is preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less. The content of each element corresponding to the other components is calculated by measuring the mass% of each element in terms of the atomic content of each element, similarly to the above-mentioned metal species M content. It is assumed that the metal acid compound dispersion of the present invention contains unavoidable impurities, not intentionally. The content of the unavoidable impurities is preferably 0.01 mass% or less.

[0095] The metal acid compound powder of the present invention is characterized by containing the metal acid compound in the above-mentioned metal acid compound dispersion of the present invention. The metal acid compound powder of the present invention includes a dried powder obtained by drying the metal acid compound dispersion of the present invention, for example by vacuum drying, and a fired powder obtained by firing the resulting dried powder. The metal acid compound powder of the present invention also includes metal acid compound powders having different physical properties, such as crystal structure, that are produced by vacuum drying or firing the metal acid compound dispersion of the present invention, and may have an amorphous structure, a single crystal structure, or a polycrystalline structure. The method for producing the metal acid compound powder of the present invention will be described later.

[0096] The metal acid compound film of the present invention is characterized by containing the metal acid compound in the above-mentioned metal acid compound dispersion of the present invention. The metal acid compound film of the present invention includes a dried film obtained by applying the metal acid compound dispersion of the present invention to the surface of a substrate and then drying, for example, vacuum drying, and a fired film obtained by firing the obtained dried film. The metal acid compound film of the present invention also includes a metal acid compound film having different physical properties such as a crystal structure, which is generated by vacuum drying or firing the metal acid compound dispersion of the present invention, and may be an amorphous structure, a single crystal structure, or a polycrystalline structure. Since the metal compound, which is the raw material of the metal acid compound film of the present invention, has high chemical resistance, the high temperature characteristics (for example, protection from deterioration of the substrate due to heat, etc.) and chemical resistance of the substrate can be improved by covering the surface of the substrate with the metal acid compound film of the present invention. The method for producing the metal acid compound film of the present invention will be described later.

[0097] The coating agent of the present invention is characterized by containing the above-mentioned metal acid compound dispersion of the present invention. The coating agent of the present invention contains the metal acid compound dispersion of the present invention, which has high dispersibility in water, good solubility in water, and excellent storage stability.

[0098] The coating agent of the present invention is characterized by containing the above-mentioned metal acid compound powder of the present invention. The coating agent of the present invention contains the metal acid compound powder of the present invention, which has high dispersibility in water, good solubility in water, and excellent storage stability.

[0099] The metal oxide compound dispersion of the present invention is characterized in that it is used for coating a positive electrode or a positive electrode material for a lithium ion secondary battery. The metal acid compound dispersion of the present invention can also be used for coating the positive electrode or positive electrode material for lithium ion secondary batteries.

[0100] The positive electrode active material for a lithium ion secondary battery of the present invention is characterized in that its surface is coated with the niobate compound contained in the above-mentioned metal acid compound dispersion of the present invention. Specific examples of the positive electrode active material for lithium ion secondary batteries include LiMn2O4 (manufactured by Merck: spinel type, particle size <0.5 μm), LiCoO2, LiNiO2, LiFeO2, Li2MnO3, LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, and LiNi 0.5 Mn 1.5 O4, LiMn 1 / 3 Co 1 / 3 Ni 1 / 3 O2, LiCo 0.2 Ni 0.4 Mn 0.4 O2, Lithium Molybdate, LiMnO4, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMnO2, etc. can be used

[0101] The lithium ion secondary battery of the present invention is characterized in that it has a positive electrode the surface of which is coated with the above-mentioned positive electrode active material for lithium ion secondary batteries of the present invention.

[0102] The method for producing the above-mentioned metal oxide compound dispersion of the present invention will be described below.

[0103] The method for producing a metal acid compound dispersion of the present invention may include a mixing step of mixing a neutralized aqueous solution of a metal compound containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium with a phosphorus compound or a phosphorus compound solution and / or a chlorine compound or a chlorine compound solution.

[0104] Specifically, a phosphorus compound or a phosphorus compound solution and / or a chlorine compound or a chlorine compound solution is added to a neutralized aqueous solution of a metal compound containing two or more kinds of metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium described below, and mixed at room temperature for 0.1 to 2 hours to obtain the metal acid compound dispersion of the present invention.

[0105] Here, the phosphorus compound may contain at least one selected from inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

[0106] Furthermore, it is preferable that the phosphorus compound contains one or more selected from phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), polyphosphoric acid (CAS number: 8071-16-1), phosphorous acid (CAS number: 13598-36-2), hypophosphorous acid (CAS number: 6303-21-5), ammonium phosphate, monoammonium phosphate (CAS number: 7722-76-1), diammonium phosphate (CAS number: 7783-28-0), ammonium pyrophosphate, and ammonium polyphosphate.

[0107] The phosphorus compound may also be a phosphorus compound solution obtained by adding pure water to the above-mentioned phosphorus compound and adjusting the concentration so that the phosphorus content in the metal oxide compound dispersion of the present invention is 0.01% by mass or more and 10% by mass or less in terms of P atoms.

[0108] Here, examples of chlorine compounds include hydrochloric acid (CAS number: 7647-01-0), hypochlorous acid (CAS number: 7790-92-3), chlorous acid (CAS number: 13898-47-0), chloric acid (CAS number: 7790-93-4), and perchloric acid (CAS number: 7601-90-3).

[0109] The chlorine compound may be a salt of the above-mentioned chlorine compound, for example, ammonium salt, amine salt, quaternary ammonium salt, lithium salt, and preferably ammonium salt or lithium salt.Specific examples include ammonium chloride (CAS number: 12125-02-9), ammonium perchlorate (CAS number: 7790-98-9), lithium chloride (CAS number: 7447-41-8), lithium perchlorate (CAS number: 7791-03-9), methylamine hydrochloride (CAS number: 593-51-1), and dimethylamine hydrochloride (CAS number: 506-59-2).

[0110] The metal oxide compound dispersion of the present invention may also be a chlorine compound solution obtained by adding pure water to the above-mentioned chlorine compound and adjusting the concentration so that the chlorine content in terms of Cl atoms in the metal oxide compound dispersion of the present invention is 0.0 mass % or more and 2.0 mass % or less.

[0111] The methods for producing neutralized aqueous solutions of metal compounds containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten and titanium, which are used in the above-mentioned method for producing a metal acid compound dispersion of the present invention, will be described below separately for a neutralized aqueous solution of a niobium compound, a neutralized aqueous solution of a tantalum compound, a neutralized aqueous solution of a molybdenum compound, a neutralized aqueous solution of a tungsten compound and a neutralized aqueous solution of a titanium compound.

[0112] The method for producing a neutralized aqueous solution of a niobium compound includes a reaction step of producing an aqueous solution of niobium fluoride, and a neutralization reaction step of adding the aqueous solution of niobium fluoride to an alkaline aqueous solution containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to produce an aqueous solution of a neutralized niobium compound.

[0113] First, the niobium fluoride aqueous solution can be prepared by reacting niobium, niobium oxide, or niobium hydroxide with hydrofluoric acid (HF) such as an aqueous solution of hydrofluoric acid to form niobium fluoride (H2NbF7), and dissolving this in water.

[0114] Here, it is preferable to adjust the niobium fluoride aqueous solution to contain 1 to 100 g / L of niobium in terms of Nb2O5 by adding water (e.g., pure water). In this case, it is preferable that the niobium content is 1 g / L or more in terms of Nb2O5, since it becomes a niobium compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the niobium content is 100 g / L or less in terms of Nb2O5, since it becomes a niobium compound hydrate that is easily soluble in water, and in order to synthesize a niobium compound hydrate that is easily soluble in water more reliably, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the niobium fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving niobium or niobium oxide.

[0115] The neutralization reaction step in which the obtained niobium fluoride aqueous solution is added to an alkaline aqueous solution containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to produce a neutralized niobium compound aqueous solution is as follows.

[0116] In the neutralization reaction step, the obtained niobium fluoride aqueous solution is first added to ammonia water, i.e., a reverse neutralization method is used to obtain a niobium-containing precipitate slurry. Then, fluoride ions are removed from the obtained niobium-containing precipitate slurry to obtain a niobium-containing precipitate from which fluoride ions have been removed.

[0117] The ammonia content of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia content is 10% by mass, niobium is less likely to remain undissolved, and niobium or niobic acid can be completely dissolved in water. On the other hand, when the ammonia content is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.

[0118] From this viewpoint, the ammonia content of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass, while the ammonia content is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.

[0119] The amount of niobium fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / Nb2O5 is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. In addition, the amount of niobium fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more, from the viewpoint of generating amines or niobic acid compounds that dissolve in dilute ammonia water. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or more, and even more preferably 40 or more.

[0120] The time for adding the niobium fluoride aqueous solution to the ammonia water is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds. That is, it is preferable to add the niobium fluoride aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the niobium fluoride aqueous solution over a long period of time, and to carry out the neutralization reaction. In the reverse neutralization step, the acidic niobium fluoride aqueous solution is added to the alkaline ammonia water, so that the neutralization reaction can be carried out while maintaining a high pH. The niobium fluoride aqueous solution and the ammonia water can be used at room temperature.

[0121] Then, fluoride ions are removed from the niobium-containing precipitate slurry obtained by the reverse neutralization method, and a niobium-containing precipitate from which fluoride ions have been removed can be obtained. Since fluorine compounds such as ammonium fluoride are present as impurities in the niobium-containing precipitate slurry obtained by the reverse neutralization method, it is preferable to remove these.

[0122] Any method can be used to remove the fluorine compounds, and examples of such methods include filtration using a membrane such as reverse osmosis filtration, ultrafiltration, and microfiltration using aqueous ammonia or pure water, centrifugation, and other known methods. When removing fluoride ions from the niobium-containing precipitate slurry, temperature control is not particularly required, and the removal may be performed at room temperature.

[0123] Specifically, the niobium-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby obtaining a niobium-containing precipitate from which the fluoride ions have been removed.

[0124] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water of 5.0 mass% or less is preferable, ammonia water of 4.0 mass% or less is more preferable, ammonia water of 3.0 mass% or less is even more preferable, and ammonia water of 2.5 mass% is particularly preferable. When the ammonia water is 5.0 mass% or less, ammonia containing ammonium ions is suitable for fluoride ions, and unnecessary cost increase can be avoided.

[0125] The niobium-containing precipitate thus obtained, from which the fluoride ions have been removed, is diluted with pure water or the like to obtain a precipitate slurry containing niobium from which the fluoride ions have been removed. The niobium content of the precipitate slurry containing niobium is determined by taking a portion of the slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce Nb2O5. The weight of the Nb2O5 thus produced can be measured, and the niobium content of the slurry can be calculated from the weight.

[0126] Next, in the neutralization reaction step, a niobium-containing precipitate slurry is obtained from which the generated fluoride ions are removed. The niobium-containing precipitate slurry from which the fluoride ions are removed, a hydroxide of element X, for example lithium hydroxide monohydrate, and pure water are mixed together and stirred at 20°C to 100°C for 0.1 to 72 hours to obtain a neutralized aqueous solution of a niobium compound.

[0127] In addition, as another example of the method for producing a neutralized aqueous solution of a niobium compound, the method may include a reaction step of producing an aqueous solution of niobium fluoride, and a neutralization reaction step of adding the aqueous solution of niobium fluoride to an alkaline aqueous solution containing an organic nitrogen compound to produce an aqueous solution of a neutralized niobium compound.

[0128] Here, in the other example of the method for producing a neutralized aqueous solution of a niobium compound, the steps up to obtaining a niobium-containing precipitate slurry from which fluoride ions have been removed are similar to those in the above-mentioned method for producing a neutralized aqueous solution of a niobium compound, and therefore detailed description thereof will be omitted.

[0129] In the same manner as in the above-mentioned method for producing a neutralized aqueous solution of a niobium compound, the obtained niobium-containing precipitate slurry from which fluoride ions have been removed, an organic nitrogen compound, and pure water are mixed together, and the resulting mixture is kept at 5°C to 90°C for 0.1 to 48 hours with stirring, to obtain a neutralized aqueous solution of a niobium compound.

[0130] The organic nitrogen compound to be mixed with the niobium-containing precipitation slurry is preferably an aliphatic amine, an aromatic amine, an amino alcohol, an amino acid, a polyamine, a quaternary ammonium, a guanidine compound, or an azole compound, as described above, and more preferably an aliphatic amine and / or a quaternary ammonium compound.

[0131] From the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine content in the niobium-containing precipitation slurry is 40 mass% or less, more preferably 20 mass% or less. From the same viewpoint, the aliphatic amine is preferably mixed so that the aliphatic amine content in the niobium-containing precipitation slurry is 0.1 mass% or more, more preferably 1 mass% or more, and may be 5 mass% or more, or may be 10 mass% or more. The aliphatic amine is more preferably methylamine or dimethylamine.

[0132] From the viewpoint of solubility, the quaternary ammonium compound is preferably mixed so that the content of the quaternary ammonium compound in the niobium-containing precipitation slurry is 40% by mass or less, and more preferably 20% by mass or less. From the same viewpoint, the quaternary ammonium compound is preferably mixed so that the content of the quaternary ammonium compound in the niobium-containing precipitation slurry is 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. The quaternary ammonium compound is more preferably tetramethylammonium hydroxide (TMAH) or tetraethylammonium hydroxide (TEAH).

[0133] The method for producing a neutralized aqueous solution of a tantalum compound includes a reaction step of adding hydrogen peroxide to an aqueous solution of tantalum fluoride to produce an aqueous solution of a tantalum compound, and a neutralization reaction step of adding the aqueous solution of a tantalum compound to an alkaline aqueous solution containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to produce a neutralized aqueous solution of a tantalum compound.

[0134] First, the tantalum fluoride aqueous solution can be prepared by reacting tantalum, tantalum oxide, or tantalum hydroxide with hydrofluoric acid (HF) such as an aqueous solution of hydrofluoric acid to form tantalum fluoride (H2TaF7), which is then dissolved in water.

[0135] Here, it is preferable to adjust the acidic tantalum solution containing fluoride ions, for example, the tantalum fluoride aqueous solution, to contain tantalum at 1 to 100 g / L in terms of Ta2O5 by adding water (for example, pure water). In this case, it is preferable that the tantalum content is 1 g / L or more in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that the tantalum content is 10 g / L or more, and even more preferable that the content is 20 g / L or more. On the other hand, it is preferable that the tantalum content is 100 g / L or less in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tantalic acid compound hydrate that is easily soluble in water, it is more preferable that the content is 90 g / L or less, even more preferable that the content is 80 g / L or less, and particularly preferable that the content is 70 g / L or less. In addition, the pH of the tantalum fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving tantalum or tantalum oxide.

[0136] Next, in the reaction step of adding hydrogen peroxide to the tantalum fluoride aqueous solution to produce a tantalum compound aqueous solution, the hydrogen peroxide solution is added to the tantalum fluoride aqueous solution and mixed to obtain a tantalum compound aqueous solution. It is presumed that at least a portion of the obtained tantalum compound aqueous solution forms a peroxo complex.

[0137] Here, the hydrogen peroxide content of the hydrogen peroxide solution added to the tantalum fluoride aqueous solution is preferably 0.5% by mass to 35% by mass. Moreover, hydrogen peroxide is preferably added so that the molar ratio H2O2 / Ta of hydrogen peroxide to tantalum is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing.

[0138] The neutralization reaction step in which the obtained aqueous solution of a tantalum compound is added to an alkaline aqueous solution containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to produce a neutralized aqueous solution of a tantalum compound is as follows.

[0139] In the neutralization reaction step, the obtained aqueous tantalum compound solution is first added to aqueous ammonia, i.e., a reverse neutralization method is used to obtain a tantalum-containing precipitate slurry, and then fluoride ions are removed from the obtained tantalum-containing precipitate slurry to obtain a tantalum-containing precipitate from which fluoride ions have been removed.

[0140] The ammonia content of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia content is 10% by mass, tantalum is less likely to remain undissolved, and tantalum or tantalic acid can be completely dissolved in water. On the other hand, when the ammonia content is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.

[0141] From this viewpoint, the ammonia content of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia content is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.

[0142] The amount of tantalum fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / Ta is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. In addition, from the viewpoint of generating amines or tantalic acid compounds that dissolve in dilute ammonia water, the amount of tantalum fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0143] The time for adding the tantalum fluoride aqueous solution to the ammonia water is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to add the tantalum fluoride aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the tantalum fluoride aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, since the acidic tantalum fluoride aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The tantalum fluoride aqueous solution and the ammonia water can be used at room temperature.

[0144] Then, by removing fluoride ions from the tantalum-containing precipitate slurry obtained by the reverse neutralization method, a tantalum-containing precipitate from which fluoride ions have been removed can be obtained. Since fluorine compounds such as ammonium fluoride are present as impurities in the tantalum-containing precipitate slurry obtained by the reverse neutralization method, it is preferable to remove these.

[0145] Any method can be used to remove the fluorine compounds, and examples of such methods include filtration using a membrane such as reverse osmosis filtration, ultrafiltration, and microfiltration using aqueous ammonia or pure water, centrifugation, and other known methods. When removing fluoride ions from the tantalum-containing precipitate slurry, there is no particular need to adjust the temperature, and the removal can be carried out at room temperature.

[0146] Specifically, the tantalum-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby obtaining a tantalum-containing precipitate from which the fluoride ions have been removed. Note that by repeating the washing, the hydrogen peroxide added in the reaction step is also removed.

[0147] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water having a concentration of 1% by mass or more and 35% by mass or less is preferable. With such ammonia water, ammonia is suitable for fluoride ions, and unnecessary cost increases can be avoided.

[0148] Next, in the neutralization reaction step, the tantalum-containing precipitate from which the generated fluoride ions have been removed is diluted with pure water or the like to obtain a tantalum-containing precipitate slurry from which the fluoride ions have been removed. The tantalum-containing precipitate slurry from which the fluoride ions have been removed, a hydroxide of element X, for example lithium hydroxide monohydrate, and pure water are mixed together and kept at 5°C to 100°C for 0.1 to 72 hours with stirring to obtain a neutralized aqueous solution of a tantalum compound.

[0149] Another example of the method for producing a neutralized aqueous solution of a tantalum compound may include a reaction step of adding hydrogen peroxide to an aqueous solution of tantalum fluoride to produce an aqueous solution of a tantalum compound, and a neutralization reaction step of adding the aqueous solution of a tantalum compound to an alkaline aqueous solution containing an organic nitrogen compound to produce a neutralized aqueous solution of a tantalum compound.

[0150] Here, in this other example of the method for producing a neutralized aqueous solution of a tantalum compound, the steps up to obtaining a tantalum-containing precipitate slurry from which fluoride ions have been removed are similar to those in the above-mentioned method for producing a neutralized aqueous solution of a tantalum compound, and therefore a detailed description thereof will be omitted.

[0151] In the same manner as in the above-described method for producing a neutralized aqueous solution of a tantalum compound of the present invention, the obtained tantalum-containing precipitate slurry from which fluoride ions have been removed, an organic nitrogen compound, and pure water are mixed together, and the mixture is stirred and maintained at 5°C to 90°C for 0.1 to 48 hours, thereby obtaining a neutralized aqueous solution of a tantalum compound.

[0152] As described above, the organic nitrogen compound to be mixed with the tantalum-containing precipitation slurry is preferably an aliphatic amine, an aromatic amine, an amino alcohol, an amino acid, a polyamine, a quaternary ammonium, a guanidine compound, or an azole compound, and more preferably an aliphatic amine and / or a quaternary ammonium compound.

[0153] From the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine content in the tantalum-containing precipitation slurry is 40 mass% or less, more preferably 20 mass% or less. From the same viewpoint, the aliphatic amine is preferably mixed so that the aliphatic amine content in the tantalum-containing precipitation slurry is 0.1 mass% or more, more preferably 1 mass% or more, and may be 5 mass% or more, or may be 10 mass% or more. The aliphatic amine is more preferably methylamine or dimethylamine.

[0154] From the viewpoint of solubility, the quaternary ammonium compound is preferably mixed so that the content of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 40% by mass or less, and more preferably 20% by mass or less. From the same viewpoint, the quaternary ammonium compound is preferably mixed so that the content of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. The quaternary ammonium compound is more preferably tetramethylammonium hydroxide (TMAH) or tetraethylammonium hydroxide (TEAH).

[0155] The aqueous solution of the neutralized molybdenum compound may be prepared by dissolving commercially available lithium molybdate in pure water.

[0156] Specifically, lithium molybdate is mixed with pure water so that the molybdenum content of the final mixture is 0.001% by mass or more and 22% by mass or less in terms of Mo atoms and the molar ratio Li / Mo of lithium to molybdenum is 0.001 to 5, and the mixture is stirred while maintaining the liquid temperature at 25°C for 1 hour, thereby obtaining a neutralized aqueous solution of a molybdenum compound. When lithium molybdate is mixed with pure water, lithium hydroxide may be added. Furthermore, in order to remove ammonia components contained in the obtained neutralized aqueous solution of a molybdenum compound, the following concentration adjustment step may be performed. In the concentration adjustment step, for example, the mixture is heated and stirred at 60°C to 90°C for 1 hour to 100 hours, and then cooled to room temperature. Thereafter, a solvent (pure water, etc.) is added to replenish the evaporated solvent (pure water, etc.). The amount of the solvent added is adjusted so that the molybdenum content of the neutralized aqueous solution of a molybdenum compound after the removal of the ammonia components is equal to the molybdenum content of the neutralized aqueous solution of a molybdenum compound before the removal of the ammonia components.

[0157] The method for producing a neutralized aqueous solution of a tungsten compound includes a step of mixing ammonium paratungstate, an alkaline aqueous solution containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and pure water, and maintaining the mixture at 20°C to 100°C while stirring to obtain a neutralized aqueous solution of a tungsten compound.

[0158] A mixture of ammonium paratungstate, lithium hydroxide monohydrate, which is an alkaline aqueous solution containing ammonium paratungstate, one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and pure water is stirred and held at 15°C to 100°C for 5 minutes to 1 hour to obtain a neutralized aqueous solution of a tungsten compound. In addition, in order to remove the ammonia component contained in the obtained neutralized aqueous solution of a tungsten compound, the following concentration adjustment step may be performed. In the concentration adjustment step, for example, the mixture is heated and stirred at 60°C to 90°C for 1 hour to 100 hours, and then cooled to room temperature. Then, a solvent (pure water, etc.) is added to replenish the evaporated solvent (pure water, etc.). The amount of the solvent added is adjusted so that the tungsten content of the neutralized aqueous solution of a tungsten compound after the ammonia component is removed is equal to the tungsten content of the neutralized aqueous solution of a tungsten compound before the ammonia component is removed.

[0159] Another example of the method for producing a neutralized aqueous solution of a tungsten compound includes a process including the steps of adding an acidic tungsten aqueous solution containing 1 to 100 g / L of tungsten calculated as WO3 to a 10 to 30 mass % aqueous ammonia solution to produce a tungsten-containing precipitate, adding an organic nitrogen compound to the tungsten-containing precipitate slurry obtained by turning the tungsten-containing precipitate into a slurry form to produce a tungsten acid dispersion, and adding lithium hydroxide and pure water to the tungsten acid dispersion to produce a neutralized aqueous solution of a tungsten compound.

[0160] Specifically, in the process of adding an acidic tungsten aqueous solution containing 1 to 100 g / L of tungsten calculated as WO3 to a 10 to 30 mass % ammonia aqueous solution to generate a tungsten-containing precipitate, the acidic tungsten aqueous solution refers to a tungsten sulfate aqueous solution obtained by solvent extraction of a solution in which tungsten is dissolved in an acidic aqueous solution containing sulfuric acid.

[0161] Here, the tungsten sulfate aqueous solution is preferably adjusted to contain 1 to 100 g / L of tungsten in terms of WO3 by adding water (e.g., pure water). In this case, it is preferable that the tungsten content is 1 g / L or more in terms of WO3, since it is a tungsten acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the tungsten content is 100 g / L or less in terms of WO3, since it is a tungsten acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tungsten acid compound hydrate that is easily soluble in water, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the tungsten sulfate aqueous solution is preferably 2 or less, and more preferably 1 or less, from the viewpoint of completely dissolving tungsten or tungsten oxide.

[0162] When the tungsten sulfate aqueous solution is added to the ammonia aqueous solution, in the so-called reverse neutralization method, it is preferable to add the tungsten sulfate aqueous solution to a 10 mass % to 30 mass % ammonia aqueous solution, that is, to obtain a slurry of a tungsten acid compound hydrate, that is, a slurry of a tungsten-containing precipitate, by the reverse neutralization method.

[0163] The ammonia content of the aqueous ammonia solution used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia content is 10% by mass, tungsten is less likely to remain undissolved, and tungsten or tungsten oxide can be completely dissolved in water. On the other hand, when the ammonia content is 30% by mass or less, it is preferably close to a saturated aqueous solution of ammonia.

[0164] From this viewpoint, the ammonia content of the aqueous ammonia solution is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass, while the ammonia content is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.

[0165] In the reverse neutralization, the amount of tungsten sulfate aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / WO3 is 0.1 or more and 300 or less, more preferably 5 or more and 200 or less. In addition, the tungsten sulfate aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / SO4 2- The molar ratio of NH3 / SO4 is preferably 3.0 or more, more preferably 10.0 or more, and even more preferably 20.0 or more. On the other hand, from the viewpoint of cost reduction, the NH3 / SO4 2- The molar ratio of is preferably 200 or less, more preferably 150 or less, and even more preferably 100 or less.

[0166] In the reverse neutralization, the time for adding the tungsten sulfate aqueous solution to the ammonia water is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds. That is, it is preferable to add the tungsten sulfate aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the tungsten sulfate aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, in the reverse neutralization, since the acidic tungsten sulfate aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The tungsten sulfate aqueous solution and the ammonia water can be used at room temperature.

[0167] The sulfur content is then removed from the slurry of the tungsten-containing precipitate obtained by the reverse neutralization method to produce a tungsten-containing precipitate from which the sulfur content has been removed. Since the slurry of the tungsten-containing precipitate obtained by the reverse neutralization method contains, as impurities, sulfate ions that remain without reacting with tungsten or tungsten oxide and sulfur content in the form of hydrogen sulfate ions, it is preferable to remove these.

[0168] Any method for removing sulfur may be used, and for example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, centrifugation, or other known methods may be used. Note that, when removing sulfur from the slurry of the tungsten-containing precipitate, temperature control is not particularly required, and the removal may be performed at room temperature.

[0169] Specifically, the slurry of the tungsten-containing precipitate obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the conductivity of the slurry of the tungsten-containing precipitate becomes 500 μS / cm or less, thereby obtaining a tungsten-containing precipitate from which the sulfur content has been removed. The conductivity was measured by adjusting the liquid temperature of the slurry of the tungsten-containing precipitate to 25° C., immersing the measuring part of a conductivity meter (ASCON2 manufactured by AS ONE CORPORATION) in the supernatant liquid of the slurry of the precipitate, and reading the value after the conductivity value stabilized.

[0170] The cleaning solution used to remove the sulfur content is preferably ammonia water. Specifically, ammonia water of 5.0 mass% or less is preferable, ammonia water of 4.0 mass% or less is more preferable, ammonia water of 3.0 mass% or less is even more preferable, and ammonia water of 2.5 mass% is particularly preferable. When the ammonia water is 5.0 mass% or less, ammonia containing ammonium ions is suitable for the sulfur content, and unnecessary cost increases can be avoided.

[0171] Next, in the step of adding an organic nitrogen compound to the tungsten-containing precipitate slurry obtained by making the tungsten-containing precipitate into a slurry, the tungsten-containing precipitate slurry is obtained by diluting the tungsten-containing precipitate from which sulfur has been removed with pure water or the like to make a slurry. The tungsten content of the tungsten-containing precipitate slurry from which sulfur has been removed is measured by taking a part of the slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce WO3. The weight of the WO3 thus produced can be measured, and the tungsten content of the slurry can be calculated from the weight.

[0172] Then, an organic nitrogen compound is mixed with the tungsten-containing precipitate slurry from which the sulfur content has been removed, thereby obtaining a tungstic acid dispersion.

[0173] Specifically, the obtained tungsten-containing precipitate slurry is added to an organic nitrogen compound and mixed with pure water so that the tungsten content of the final mixture is 0.1 mass % or more and 40 mass % or less in terms of WO3, and the mixture is stirred while maintaining the liquid temperature at room temperature (25°C) for 1 hour, thereby obtaining a colorless and transparent tungstic acid dispersion.

[0174] The organic nitrogen compound mixed with the tungsten-containing precipitation slurry is preferably an aliphatic amine and / or a quaternary ammonium.

[0175] Here, from the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine content in the tungsten-containing precipitation slurry is 40 mass% or less, more preferably 0.1 mass% to 30 mass%, even more preferably 0.5 mass% to 20 mass%, and particularly preferably 1 mass% to 10 mass%. The aliphatic amine is more preferably methylamine, dimethylamine, ethylamine, trimethylamine, or a mixture thereof.

[0176] On the other hand, from the viewpoint of solubility, the quaternary ammonium is preferably mixed so that the content of the quaternary ammonium in the tungsten-containing precipitation slurry is 40 mass% or less, more preferably 0.1 mass% or more and 30 mass% or less, even more preferably 0.5 mass% or more and 20 mass% or less, and particularly preferably 1 mass% or more and 10 mass% or less. It is more preferable that the quaternary ammonium is tetramethylammonium hydroxide (TMAH) or tetraethylammonium hydroxide (TEAH).

[0177] Furthermore, the organic nitrogen compound to be mixed with the tungsten-containing precipitation slurry may be a mixture of two or more of aliphatic amines or quaternary ammonium, rather than one of them. For example, a mixture of two or more organic nitrogen compounds such as methylamine and tetramethylammonium hydroxide (TMAH), dimethylamine and tetramethylammonium hydroxide (TMAH), or methylamine and dimethylamine, or a mixture of three or more organic nitrogen compounds such as methylamine, dimethylamine, and tetramethylammonium hydroxide (TMAH) may be used, and may be appropriately changed according to the application.

[0178] The tungstic acid dispersion thus produced, lithium hydroxide monohydrate, and pure water are weighed out so that the molar ratio Li / W of lithium to tungsten in the final mixture is 0.2 or more and 20 or less, and the mixture obtained by mixing them is kept at 10°C to 100°C for 1 minute to 3 days while stirring, thereby obtaining a neutralized aqueous solution of a tungsten compound.

[0179] Specifically, a tungsten compound neutralized aqueous solution is obtained by mixing and stirring a tungsten acid dispersion, lithium hydroxide monohydrate, and pure water so that the tungsten content of the final mixture is 0.001 mass% or more and 23 mass% or less in terms of W atoms and the molar ratio Li / W of lithium to tungsten is 0.001 mass% or more and 5 or less. In addition, the following concentration adjustment step may be performed to remove ammonia components contained in the obtained tungsten compound neutralized aqueous solution. In the concentration adjustment step, for example, the mixture is heated and stirred at 60°C to 90°C for 1 hour to 100 hours, and then cooled to room temperature. Then, a solvent (pure water, etc.) is added to replenish the evaporated solvent (pure water, etc.). The amount of the solvent added is adjusted so that the tungsten content of the tungsten compound neutralized aqueous solution after the ammonia components are removed is equal to the tungsten content of the tungsten compound neutralized aqueous solution before the ammonia components are removed.

[0180] The method for producing a neutralized aqueous solution of a titanium compound includes the steps of mixing a titanium salt solution with aqueous ammonia to produce a neutralized reaction solution, washing a titanium-containing precipitate produced in the neutralized reaction solution, and mixing the washed titanium-containing precipitate with a quaternary ammonium salt and water to obtain a neutralized aqueous solution of a titanium compound.

[0181] The titanium salt solution may be any solution in which titanium is dissolved, and examples thereof include an aqueous solution of titanyl sulfate, an aqueous solution of titanyl chloride, and an aqueous solution of titanium fluoride.

[0182] Here, the titanyl sulfate aqueous solution is obtained by dissolving titanyl sulfate in hot water. The titanyl sulfate aqueous solution is preferably prepared so as to contain 8 to 15 mass % of titanium in terms of TiO2.

[0183] The above-mentioned titanium salt solution, for example, the titanyl sulfate aqueous solution, can be mixed with ammonia water to produce a neutralized reaction solution. Here, it is preferable to carry out so-called reverse neutralization, in which the titanyl sulfate aqueous solution is added to ammonia water to cause a reaction.

[0184] The ammonia content of the aqueous ammonia solution used for reverse neutralization is preferably 10% by mass to 40% by mass. If the ammonia content is 25% by mass, titanium is less likely to remain undissolved, and titanium or titanium oxide can be completely dissolved in water. On the other hand, if the ammonia content is 30% by mass or less, it is preferably close to a saturated aqueous ammonia solution.

[0185] From this viewpoint, the ammonia content of the aqueous ammonia solution is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass, while the ammonia content is preferably 30% by mass or less, more preferably 35% by mass or less, and even more preferably 40% by mass or less.

[0186] In the reverse neutralization, the amount of titanyl sulfate solution added to the ammonia water is preferably such that the molar ratio of NH3 / TiO2 is 1 or more and 200 or less, more preferably 10 or more and 100 or less. In addition, the titanyl sulfate solution added to the ammonia water is preferably such that the molar ratio of NH3 / SO4 2- The molar ratio of NH3 / SO4 is preferably 1 or more, more preferably 5 or more, and even more preferably 10 or more. On the other hand, from the viewpoint of cost reduction, 2- The molar ratio of is preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less.

[0187] In the reverse neutralization, the time for adding the titanyl sulfate aqueous solution to the ammonia water is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds. That is, rather than gradually adding the titanyl sulfate aqueous solution over a period of time, it is preferable to add it to the ammonia water in as short a time as possible, for example, all at once, and carry out the neutralization reaction. In addition, in the reverse neutralization, since the acidic titanyl sulfate aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH.

[0188] By washing the slurry of the titanium-containing precipitate in the neutralization reaction solution obtained by reverse neutralization, impurities are removed and a titanium-containing precipitate is obtained. The slurry of the titanium-containing precipitate obtained by reverse neutralization contains unnecessary components other than titanium or titanium oxide hydrates or ions and ammonia, such as sulfate compounds such as ammonium sulfate, as impurities, and it is preferable to remove these.

[0189] Any method for washing, for example, a method for removing sulfate compounds, may be used. For example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, as well as centrifugation and other known methods may be used. Note that this step may be performed at room temperature, and there is no particular need to adjust the temperature of each step.

[0190] Then, to the titanium-containing precipitate obtained after removing the impurities, a dispersion medium such as water is added, and a quaternary ammonium salt is added, and the mixture is stirred as necessary to promote the reaction, thereby preparing a neutralized aqueous solution of the titanium compound.

[0191] Examples of the quaternary ammonium salt include tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, methyltripropylammonium hydroxide, methyltributylammonium hydroxide, tetrapentylammonium hydroxide, tetrahexylammonium hydroxide, ethyltrimethylammonium hydroxide, dimethyldiethylammonium hydroxide, benzyltrimethylammonium hydroxide, hexadecyltrimethylammonium hydroxide, and (2-hydroxyethyl)trimethylammonium hydroxide.

[0192] As described above, the amount of quaternary ammonium salt added is preferably such that a quaternary ammonium salt containing 0.44 mol or more of quaternary ammonium is mixed per mol of titanium contained in the titanium-containing precipitate after washing, since a larger amount of quaternary ammonium can increase the solubility of titanium or titanic acid in water. On the other hand, from the viewpoint that too much quaternary ammonium may cause problems such as impeding film formation or inhibiting catalytic action, it is preferable to mix a quaternary ammonium salt having 1.0 mol or less of quaternary ammonium per mol of titanium contained in the titanium-containing precipitate after washing.

[0193] Each step in the above-mentioned method for producing a neutralized aqueous titanium compound solution may be carried out at room temperature, and there is no particular need to adjust the temperature of each step.

[0194] In addition, titanium alkoxide may be used as the titanium compound neutralization aqueous solution. Examples of titanium alkoxide include titanium tetraisopropoxide, titanium i-propoxide, titanium n-butoxide, titanium 2-ethylhexoxide, titanium tert-butoxide, titanium stearyl alkoxide, and titanium tetraisopropoxide.

[0195] As another example of the method for producing a metal acid compound dispersion liquid of the present invention, the method may include a step of mixing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements with a phosphorus compound, or a phosphorus compound solution, and / or a chlorine compound, or a chlorine compound solution to produce a phosphorus compound mixed solution and / or a chlorine compound mixed solution, and a mixing step of mixing the phosphorus compound mixed solution and / or the chlorine compound mixed solution with a neutralized aqueous solution of a metal compound containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium.

[0196] First, one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements are mixed with a phosphorus compound, or a phosphorus compound solution, and / or a chlorine compound, or a chlorine compound solution to generate a phosphorus compound mixed solution and / or a chlorine compound mixed solution.

[0197] Here, the one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements include, for example, lithium hydroxide monohydrate.

[0198] The phosphorus compound may contain at least one selected from inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

[0199] Furthermore, it is preferable that the phosphorus compound contains one or more selected from phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), polyphosphoric acid (CAS number: 8071-16-1), phosphorous acid (CAS number: 13598-36-2), hypophosphorous acid (CAS number: 6303-21-5), ammonium phosphate, monoammonium phosphate (CAS number: 7722-76-1), diammonium phosphate (CAS number: 7783-28-0), ammonium pyrophosphate, and ammonium polyphosphate.

[0200] The phosphorus compound may also be a phosphorus compound solution obtained by adding pure water to the above-mentioned phosphorus compound and adjusting the concentration so that the phosphorus content in the metal oxide compound dispersion of the present invention is 0.01% by mass or more and 10% by mass or less in terms of P atoms.

[0201] Here, examples of chlorine compounds include hydrochloric acid (CAS number: 7647-01-0), hypochlorous acid (CAS number: 7790-92-3), chlorous acid (CAS number: 13898-47-0), chloric acid (CAS number: 7790-93-4), and perchloric acid (CAS number: 7601-90-3).

[0202] The chlorine compound may be a salt of the above-mentioned chlorine compound, for example, ammonium salt, amine salt, quaternary ammonium salt, lithium salt, and preferably ammonium salt or lithium salt.Specific examples include ammonium chloride (CAS number: 12125-02-9), ammonium perchlorate (CAS number: 7790-98-9), lithium chloride (CAS number: 7447-41-8), lithium perchlorate (CAS number: 7791-03-9), methylamine hydrochloride (CAS number: 593-51-1), and dimethylamine hydrochloride (CAS number: 506-59-2).

[0203] The metal oxide compound dispersion of the present invention may also be a chlorine compound solution obtained by adding pure water to the above-mentioned chlorine compound and adjusting the concentration so that the chlorine content in terms of Cl atoms in the metal oxide compound dispersion of the present invention is 0.0 mass % or more and 2.0 mass % or less.

[0204] The phosphorus compound mixed solution and / or the chlorine compound mixed solution are mixed with an aqueous neutralized metal compound solution containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium, thereby obtaining the metal acid compound dispersion of the present invention.

[0205] The aqueous solution of neutralized metal compounds containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium can be an aqueous solution of neutralized metal compounds obtained by the above-mentioned method for producing an aqueous solution of neutralized metal compounds.

[0206] In order to remove the ammonia component contained in the metal acid compound dispersion of the present invention obtained by the above-mentioned production method, the following concentration adjustment step may be carried out. In the concentration adjustment step, for example, the mixture is heated and stirred at 60°C to 90°C for 1 hour to 100 hours, and then cooled to room temperature. Thereafter, a solvent (pure water, etc.) is added to replenish the evaporated solvent (pure water, etc.). The amount of the solvent added is adjusted so that the content of the metal species M in the metal acid compound dispersion of the present invention after the ammonia component has been removed is equal to the content of the metal species M in the metal acid compound dispersion of the present invention before the ammonia component has been removed.

[0207] Specifically, the metal acid compound dispersion of the present invention is obtained by mixing and stirring the obtained metal compound neutralized aqueous solution with a phosphorus compound or a phosphorus compound solution and / or a chlorine compound or a chlorine compound solution so that the content of the metal species M in the final mixture is 0.1% by mass or more and 30% by mass or less in terms of the metal species M atom. The composition ratio of each component in the metal acid compound dispersion of the present invention thus obtained is preferably as follows:

[0208] When the element X contained in the metal acid compound dispersion of the present invention is lithium, the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water. When the element X contained in the metal acid compound dispersion of the present invention is an element X selected from alkali metal elements and / or alkaline earth metal elements other than lithium, the molar ratio x / (P+Cl) of the total amount (x) of element X to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water. The element X may be a combination of lithium and other alkali metal elements and / or alkaline earth metal elements, or a combination of alkali metal elements other than lithium and / or alkaline earth metal elements.

[0209] When the element X contained in the metal acid compound dispersion of the present invention is lithium, the molar ratio Li / P of lithium (Li) to the total amount (P) of phosphorus compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water. When the element X contained in the metal acid compound dispersion of the present invention is an element X selected from alkali metal elements other than lithium and / or alkaline earth metal elements, the molar ratio x / P of the total amount (x) of element X to the total amount (P) of phosphorus compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water.

[0210] Furthermore, the molar ratio m / (P+Cl) of the total amount (m) of metal species M contained in the metal acid compound dispersion of the present invention to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds is preferably 0.01 or more and 10 or less, in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0211] Furthermore, the molar ratio m / P of the total amount (m) of metal species M contained in the metal acid compound dispersion of the present invention to the total amount (P) of phosphorus compounds is preferably 0.01 or more and 10 or less, in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0212] In addition, when the element X contained in the metal acid compound dispersion of the present invention is lithium, the molar ratio Li / m of lithium (Li) to the total amount (m) of metal species M is preferably 0.01 to 10 in terms of improving dispersibility and solubility in water, more preferably 0.05 to 9 in terms of improving dispersibility and solubility in water, even more preferably 0.1 to 8 in terms of improving dispersibility and solubility in water, and particularly preferably 1 to 7 in terms of improving dispersibility and solubility in water. In addition, when the element X contained in the metal acid compound dispersion of the present invention is an element X selected from alkali metal elements other than lithium and / or alkaline earth metal elements, the molar ratio m / x of the total amount (x) of element X to the total amount (m) of metal species M is preferably 0.01 to 10 in terms of improving dispersibility and solubility in water, more preferably 0.05 to 9 ...1 to 8 in terms of improving dispersibility and solubility in water, and particularly preferably 1 to 7 in terms of improving dispersibility and solubility in water. In addition, the element X may be a plurality of elements, including lithium and other alkali metal elements and / or alkaline earth metal elements, or a plurality of elements selected from alkali metal elements other than lithium and / or alkaline earth metal elements.

[0213] The order of adding the metal compound neutralization aqueous solution, the phosphorus compound or phosphorus compound solution and / or the chlorine compound or chlorine compound solution, the one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, the pure water, etc., which are mixed in the mixing step of the method for producing a metal acid compound dispersion of the present invention, is not limited to the order described above and can be changed as appropriate.

[0214] The method for producing the metal acid compound powder containing the metal acid compound in the metal acid compound dispersion of the present invention will be described below.

[0215] Among the metal acid compound powders, a method for producing a dry powder of a metal acid compound involves placing the metal acid compound dispersion obtained by the method for producing a metal acid compound dispersion of the present invention described above in a static furnace and drying, for example vacuum drying, for 1 to 72 hours at a heating temperature of about 60°C to 200°C, whereby the water content of the metal acid compound dispersion of the present invention evaporates, and a dry powder of the metal acid compound containing crystal particles of the metal acid compound contained in the metal acid compound dispersion of the present invention is obtained.

[0216] On the other hand, a method for producing a calcined powder of a metal acid compound includes vacuum drying the metal acid compound dispersion liquid of the present invention as described above, placing the obtained dry powder of the metal acid compound in a static furnace, and calcining it in the atmosphere at a calcination temperature of 300°C or more and 1,200°C or less for a calcination time of 1 hour or more and 72 hours or less, thereby obtaining a calcined powder of the metal acid compound.

[0217] The above-mentioned dry powder and calcined powder of the metal acid compound may be pulverized and used as the metal acid compound powder. Regardless of whether or not the powder is pulverized, the above-mentioned dry powder and calcined powder of the metal acid compound may be classified using a sieve, and the undersize (fine particle side) obtained may be used as the metal acid compound powder. The oversize (coarse particle side) may be pulverized again and classified before use. It is also possible to combine pulverization and classification using a vibrating sieve into which iron balls coated with nylon or fluororesin are charged as pulverizing media. By combining classification and pulverization in this way, even if there is a metal acid compound powder that is too large, it is possible to remove it. Specifically, when classifying using a sieve, it is preferable to use one with an opening of 150 μm to 1,000 μm. If it is 150 μm to 1,000 μm, the proportion of the oversize powder will not be too high, so that re-pulverization will not be repeated, and the metal acid compound powder that needs to be re-pulverized will not be classified as the undersize powder.

[0218] The metal acid compound powder thus obtained is mixed with water or an organic solvent as a dispersion medium, and wet-pulverized using a medium such as beads to obtain a metal acid compound powder dispersion. Here, examples of the organic solvent used as the dispersion medium include alcohols, esters, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, ethers, and mixed solvents thereof. Furthermore, in order to improve the film-forming properties of the metal acid compound film using the metal acid compound powder dispersion, a binder such as a resin component may be added. Examples of the resin component used as a binder include acrylic resin, polyurethane, epoxy resin, polystyrene, polycarbonate, glycol resin, cellulose resin, and mixed resins and copolymer resins thereof.

[0219] Further, a method for producing a metal acid compound film containing a metal acid compound in the metal acid compound dispersion of the present invention will be described below.

[0220] Among metal acid compound films, a method for producing a metal acid compound dry film includes a coating step of coating a metal acid compound dispersion onto the surface of a substrate, and a film drying step of drying the metal acid compound dispersion coated onto the surface of the substrate to obtain a dry film.

[0221] Specifically, the metal acid compound dispersion obtained by the above-mentioned method for producing a metal acid compound dispersion of the present invention is dropped onto the surface of a substrate using a syringe while being filtered, for example, with a filter having a pore size of 1 μm, as necessary, and then applied by spin coating (700 rpm, 10 seconds, followed by 1500 rpm, 30 seconds).Then, the substrate is dried at 110° C. for 30 minutes to form a metal acid compound dry film on the surface of the substrate.

[0222] Of the metal acid compound films, the method for producing a calcined metal acid compound film includes a coating step of coating a metal acid compound dispersion onto the surface of a substrate, a film drying step of drying the metal acid compound dispersion coated on the surface of the substrate under atmospheric pressure or under vacuum to obtain a dried film, and a film calcination step of calcining the dried film under atmospheric pressure at a calcination temperature of 300°C or higher and 1,200°C or lower for a calcination time of 1 hour or higher and 12 hours or lower to obtain a calcined film.

[0223] Specifically, as described above, the metal acid compound dispersion is applied to the surface of a substrate, and the substrate on which a dry metal acid compound film is formed by drying is placed in a static furnace and baked in air at a baking temperature of 300°C or higher and 1,200°C or lower for a baking time of 1 hour or higher and 12 hours or lower, thereby forming a baked metal acid compound film on the surface of the substrate.

[0224] Further, a method for producing a positive electrode active material for a lithium ion secondary battery coated with a metal acid compound contained in the metal acid compound dispersion of the present invention will be described below.

[0225] The method includes a step of mixing the metal acid compound dispersion of the present invention, a positive electrode active material, and, if necessary, an aqueous lithium hydroxide solution to produce a positive electrode active material slurry for a battery containing a metal acid compound, and a step of drying the positive electrode active material slurry for a battery containing the metal acid compound.

[0226] First, a battery positive electrode active material, for example, LiMn2O4 (manufactured by Merck: spinel type, particle size <0.5 μm) is added to a metal acid compound dispersion obtained by diluting the metal acid compound dispersion of the present invention with pure water to obtain a slurry containing the metal acid compound. Then, while stirring the slurry containing the metal acid compound, an aqueous lithium hydroxide solution is dropped and the slurry is kept at 90° C. for 10 minutes to produce a battery positive electrode active material slurry containing the metal acid compound.

[0227] Next, the battery positive electrode active material slurry containing the metal acid compound is dried in an atmospheric drying furnace for 15 hours while maintaining the furnace temperature at 110°C, thereby producing a positive electrode active material for a lithium ion secondary battery coated with the metal acid compound.

[0228] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention

[0229] The metal acid compound dispersion of the present invention has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. Furthermore, the method for producing a metal acid compound dispersion of the present invention can produce a metal acid compound dispersion that has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. [Brief description of the drawings]

[0230] [Figure 1] 1 is a table showing the compositions of metal acid compound dispersions according to Examples 1 to 19 of the present invention and Comparative Examples 1 to 4. [Diagram 2]1 is a table showing composition ratios of metal acid compound dispersions according to Examples 1 to 19 of the present invention and Comparative Examples 1 to 4. [Diagram 3] 1 is a table showing the measurement results of metal acid compound dispersions according to Examples 1 to 19 of the present invention and Comparative Examples 1 to 4. BEST MODE FOR CARRYING OUT THEINVENTION

[0231] The metal oxide compound dispersion liquid according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.

[0232] Example 1 0.3 g of pyrophosphoric acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., product name: diphosphoric acid (containing phosphoric acid), CAS number: 2466-09-3) and 26.48 g of pure water were placed in a polypropylene container, and 4.23 g of a 5 mass% aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed solution of phosphorus compounds.

[0233] Here, the 5 mass% lithium hydroxide monohydrate aqueous solution was obtained by mixing 15 g of LiOH·H2O and 285 g of pure water.

[0234] Then, 1.63 g of a neutralized aqueous solution of a niobium compound and 2.25 g of a neutralized aqueous solution of a tantalum compound, which will be described later, were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a metal acid compound dispersion liquid according to Example 1.

[0235] The neutralized aqueous solution of a niobium compound according to Example 1 was obtained as follows.

[0236] 100g of niobium pentoxide was dissolved in 200g of 55% hydrofluoric acid solution, and 830mL of pure water was added to obtain a niobium fluoride aqueous solution containing 100g / L of niobium in terms of Nb2O5 (Nb2O5=8.85% by mass). 200mL of this niobium fluoride aqueous solution was added to 1L of ammonia water (NH3 concentration 25% by mass) in less than 1 minute (NH3 / Nb2O5 molar ratio=176.9, NH3 / HF molar ratio=12.1) to obtain a reaction solution (pH11). This reaction solution was a slurry of niobium acid compound hydrate, in other words, a slurry of niobium-containing precipitate.

[0237] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a niobium-containing precipitate from which the fluoride ions had been removed. At this time, ammonia water was used as the washing liquid.

[0238] The niobium-containing precipitate from which the fluoride ions had been removed was then diluted with pure water to obtain a slurry. A portion of this slurry was dried at 110°C for 24 hours and then calcined at 1,000°C for 4 hours to produce Nb2O5, and the Nb2O5 content in the slurry was calculated from its weight.

[0239] Then, the niobium-containing precipitate slurry diluted with pure water, 5 mass% lithium hydroxide, and pure water were mixed to obtain a translucent slurry mixture. The mixture was stirred and held for 1 hour at a liquid temperature of 50°C to 100°C, for example 70°C, to obtain a neutralized aqueous solution of a niobium compound according to Example 1. The niobium content in the neutralized aqueous solution of a niobium compound according to Example 1 was 2.86 mass%, and the lithium content was 0.23 mass%.

[0240] The neutralized aqueous solution of a tantalum compound according to Example 1 was obtained as follows.

[0241] First, 137.9 g of tantalum hydroxide (Ta2O5 content 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of 55 mass% hydrofluoric acid aqueous solution, and 849 mL of pure water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 content 8.2 mass%).

[0242] To 1,000 g of this tantalum fluoride aqueous solution, 36.1 g of hydrogen peroxide solution (H2O2 content: 35 mass %) was added (H2O2 / Ta molar ratio: 1.0), and the mixture was stirred for 5 minutes to obtain an aqueous tantalum compound solution.

[0243] 1,036.1 g of this tantalum compound aqueous solution was added to 6.82 L of ammonia water (NH3 concentration 25 mass %) in less than 1 minute (NH3 / Ta molar ratio = 245, NH3 / HF molar ratio = 30.6) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of a tantalic acid compound hydrate, in other words, a slurry of a tantalum-containing precipitate.

[0244] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed, using aqueous ammonia as the washing liquid.

[0245] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 content in the tantalum-containing precipitate slurry was calculated from its weight.

[0246] Then, pure water adjusted to a temperature of 70°C to 80°C, the tantalum-containing precipitate slurry diluted with pure water, and a 5 mass% aqueous solution of lithium hydroxide monohydrate were mixed to obtain a neutralized aqueous solution of a tantalum compound according to Example 1. The tantalum content in the neutralized aqueous solution of a tantalum compound according to Example 1 was 4.06 mass%, and the lithium content was 0.14 mass%.

[0247] Example 2 In Example 2, 0.3 g of pyrophosphoric acid and 27.25 g of pure water were placed in a polypropylene container, and 4.02 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0248] Then, 2.74 g of the niobium compound neutralized aqueous solution used in Example 1 and 0.58 g of the molybdenum compound neutralized aqueous solution described below were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 2.

[0249] The neutralized aqueous solution of a molybdenum compound according to Example 2 was obtained by the above-mentioned method for producing a neutralized aqueous solution of a molybdenum compound. The molybdenum content in the neutralized aqueous solution of a molybdenum compound according to Example 2 was 2.80% by mass, and the lithium content was 0.37% by mass.

[0250] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 2 were the same as those used in Example 1.

[0251] Example 3 In Example 3, 0.31 g of pyrophosphoric acid and 26.94 g of pure water were placed in a polypropylene container, and 4.20 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0252] Then, 2.74 g of the niobium compound neutralized aqueous solution used in Example 1 and 0.88 g of the tungsten compound neutralized aqueous solution described below were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 3.

[0253] Here, the tungsten compound neutralized aqueous solution according to Example 3 was obtained by the above-mentioned method for producing a tungsten compound neutralized aqueous solution. The tungsten content in the tungsten compound neutralized aqueous solution according to Example 3 was 3.46 mass %, and the lithium content was 0.27 mass %.

[0254] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 3 were the same as those used in Example 1.

[0255] Example 4 In Example 4, 0.31 g of pyrophosphoric acid and 25.95 g of pure water were placed in a polypropylene container, and 4.34 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0256] Then, 2.74 g of the niobium compound neutralized aqueous solution used in Example 1 and 1.61 g of the titanium compound neutralized aqueous solution described below were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 4.

[0257] The neutralized aqueous solution of titanium compound according to Example 4 was obtained by the above-mentioned method for producing a neutralized aqueous solution of titanium compound. The titanium content in the neutralized aqueous solution of titanium compound according to Example 4 was 0.48 mass%.

[0258] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 4 were the same as those used in Example 1.

[0259] Example 5 In Example 5, 0.29 g of pyrophosphoric acid and 25.90 g of pure water were placed in a polypropylene container, and 4.01 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0260] Then, 1.63 g of the niobium compound neutralized aqueous solution used in Example 1, 0.57 g of the molybdenum compound neutralized aqueous solution used in Example 2, 0.88 g of the tungsten compound neutralized aqueous solution used in Example 3, and 1.59 g of the titanium compound neutralized aqueous solution used in Example 4 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 5.

[0261] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 5 were the same as those used in Example 1.

[0262] Example 6 In Example 6, 0.32 g of pyrophosphoric acid and 26.4 g of pure water were placed in a polypropylene container, and 4.17 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0263] Then, 3.72 g of the tantalum compound neutralized aqueous solution used in Example 1 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 6.

[0264] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 6 were the same as those used in Example 1.

[0265] Example 7 In Example 7, 0.29 g of pyrophosphoric acid and 25.99 g of pure water were placed in a polypropylene container, and 4.15 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0266] Then, 3.75 g of the tantalum compound neutralized aqueous solution used in Example 1 and 0.86 g of the tungsten compound neutralized aqueous solution used in Example 3 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 7.

[0267] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 7 were the same as those used in Example 1.

[0268] Example 8 In Example 8, 0.3 g of pyrophosphoric acid and 24.7 g of pure water were placed in a polypropylene container, and 4.45 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0269] Then, 3.74 g of the tantalum compound neutralized aqueous solution used in Example 1 and 1.63 g of the titanium compound neutralized aqueous solution used in Example 4 were added to the phosphorus compound mixed solution, and the mixture was stirred for 30 minutes to obtain a metal acid compound dispersion liquid of Example 8.

[0270] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 8 were the same as those used in Example 1.

[0271] Example 9 In Example 9, 0.29 g of pyrophosphoric acid and 25.00 g of pure water were placed in a polypropylene container, and 4.17 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0272] Then, 2.24 g of the tantalum compound neutralized aqueous solution used in Example 1, 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2, 0.88 g of the tungsten compound neutralized aqueous solution used in Example 3, and 1.64 g of the titanium compound neutralized aqueous solution used in Example 4 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 9.

[0273] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 9 were the same as those used in Example 1.

[0274] Example 10 In Example 10, 0.31 g of pyrophosphoric acid and 24.24 g of pure water were placed in a polypropylene container, and 3.83 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0275] Then, 1.09 g of the niobium compound neutralized aqueous solution used in Example 1, 2.23 g of the tantalum compound neutralized aqueous solution used in Example 1, 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2, 0.89 g of the tungsten compound neutralized aqueous solution used in Example 3, and 1.63 g of the titanium compound neutralized aqueous solution used in Example 4 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 10.

[0276] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 10 were the same as those used in Example 1.

[0277] Example 11 In Example 11, 0.31 g of pyrophosphoric acid and 25.98 g of pure water were placed in a polypropylene container, and 5.47 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0278] Then, 2.71 g of the niobium compound neutralized aqueous solution used in Example 1 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred for 30 minutes to obtain a metal acid compound dispersion liquid of Example 11.

[0279] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 11 were the same as those used in Example 1.

[0280] Example 12 In Example 12, 0.3 g of pyrophosphoric acid and 29.59 g of pure water were placed in a polypropylene container, and 0.79 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0281] Then, 3.75 g of the tantalum compound neutralized aqueous solution used in Example 1 and 0.6 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 12.

[0282] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 12 were the same as those used in Example 1.

[0283] (Example 13) In Example 13, 0.3 g of pyrophosphoric acid and 27.89 g of pure water were placed in a polypropylene container, and 2.48 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0284] Then, 3.75 g of the tantalum compound neutralized aqueous solution used in Example 1 and 0.6 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 13.

[0285] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 13 were the same as those used in Example 1.

[0286] Example 14 In Example 14, 0.38 g of 85% by mass phosphoric acid and 25.93 g of pure water were placed in a polypropylene container, and 4.13 g of 5% by mass lithium hydroxide monohydrate aqueous solution was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0287] Then, 3.9 g of the tantalum compound neutralized aqueous solution and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 14.

[0288] The neutralized aqueous solution of the tantalum compound of Example 14 was obtained in the same manner as the neutralized aqueous solution of the tantalum compound of Example 1, except that the neutralized aqueous solution of the tantalum compound was prepared so that the tantalum content in the neutralized aqueous solution of the tantalum compound was 3.89 mass % and the lithium content was 0.15 mass %.

[0289] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 14 was the same as that used in Example 1.

[0290] Example 15 In Example 15, 3.38 g of 1 mol / L hydrochloric acid and 23.01 g of pure water were placed in a polypropylene container, and 4.1 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous solution of chlorine compounds to obtain a mixed solution of chlorine compounds.

[0291] Then, 3.9 g of the tantalum compound neutralized aqueous solution used in Example 14 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the chlorine compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 15.

[0292] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 15 was the same as that used in Example 1.

[0293] (Example 16) In Example 16, 0.28 g of phosphonic acid and 25.97 g of pure water were placed in a polypropylene container, and 4.14 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0294] Then, 3.95 g of the tantalum compound neutralized aqueous solution used in Example 14 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 16.

[0295] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 16 was the same as that used in Example 1.

[0296] (Example 17) In Example 17, 0.73 g of 30 mass % phosphinic acid and 25.63 g of pure water were placed in a polypropylene container, and 4.14 g of 5 mass % lithium hydroxide monohydrate aqueous solution was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0297] Then, 3.91 g of the tantalum compound neutralized aqueous solution used in Example 14 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 17.

[0298] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 17 was the same as that used in Example 1.

[0299] (Example 18) In Example 18, 0.33 g of 80 mass% P2O5 polyphosphoric acid and 26.02 g of pure water were placed in a polypropylene container, and 4.12 g of 5 mass% lithium hydroxide monohydrate aqueous solution was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0300] Then, 3.9 g of the tantalum compound neutralized aqueous solution used in Example 14 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 18.

[0301] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 18 was the same as that used in Example 1.

[0302] (Example 19) In Example 19, 0.6 g of triethyl phosphate and 25.8 g of pure water were placed in a polypropylene container, and 4.13 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0303] Then, 3.9 g of the tantalum compound neutralized aqueous solution used in Example 14 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Example 19.

[0304] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 19 was the same as that used in Example 1.

[0305] Comparative Example 1 In Comparative Example 1, 0.29 g of pyrophosphoric acid and 29.68 g of pure water were placed in a polypropylene container, and 4.25 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0306] Then, 0.12 g of lithium niobate powder (manufactured by Kojundo Chemical Laboratory Co., Ltd.) and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Comparative Example 2.

[0307] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Comparative Example 1 were the same as those used in Example 1.

[0308] Comparative Example 2 In Comparative Example 2, 0.3 g of pyrophosphoric acid and 29.67 g of pure water were placed in a polypropylene container, and 4.24 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0309] Then, 0.2 g of lithium tantalate powder (manufactured by Kojundo Chemical Laboratory Co., Ltd.) and 0.59 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Comparative Example 2.

[0310] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Comparative Example 2 were the same as those used in Example 1.

[0311] Comparative Example 3 In Comparative Example 3, 3.29 g of 10 mass % sulfuric acid and 23.07 g of pure water were placed in a polypropylene container, and 4.11 g of 5 mass % lithium hydroxide monohydrate aqueous solution was added to the obtained sulfur compound aqueous solution to obtain a sulfur compound mixed solution.

[0312] Then, 3.9 g of the tantalum compound neutralized aqueous solution used in Example 14 and 0.58 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to the sulfur compound mixed solution, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Comparative Example 3.

[0313] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Comparative Example 3 was the same as that in Example 1.

[0314] Comparative Example 4 In Comparative Example 4, 4.39 g of a 5 mass% aqueous solution of lithium hydroxide monohydrate, 6.52 g of the tantalum compound neutralized aqueous solution used in Example 14, and 0.95 g of the molybdenum compound neutralized aqueous solution used in Example 2 were added to 23.15 g of pure water placed in a polypropylene container, and the mixture was stirred and mixed for 30 minutes to obtain a metal acid compound dispersion liquid of Comparative Example 4.

[0315] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Comparative Example 4 was the same as that in Example 1.

[0316] The following physical properties were measured for the metal acid compound dispersions of Examples 1 to 19 and Comparative Examples 1 to 4. The measured physical properties and the methods for measuring the physical properties are shown below, while the compositions of the metal acid compound dispersions of Examples 1 to 19 and Comparative Examples 1 to 4 are shown in Figure 1, the composition ratios of the metal acid compound dispersions of Examples 1 to 19 and Comparative Examples 1 to 4 are shown in Figure 2, and the measurement results of the metal acid compound dispersions of Examples 1 to 19 and Comparative Examples 1 to 4 are shown in Figure 3.

[0317] <Elemental analysis> If necessary, the samples were appropriately diluted with dilute hydrochloric acid, and the following mass % was measured for the metal acid compound dispersions of Examples 1 to 19 and Comparative Examples 1 to 4 using ICP optical emission spectrometry (AG-5110, manufactured by Agilent Technologies) in accordance with JIS K0116:2014: Nb mass % calculated as Nb atoms, Ta mass % calculated as Ta atoms, Mo mass % calculated as Mo atoms, W mass % calculated as W atoms, Ti mass % calculated as Ti atoms, P mass % calculated as P atoms, Li mass % calculated as Li atoms, Cl mass % calculated as Cl atoms, and S mass % calculated as S atoms.

[0318] <pH measurement> The pH of the metal acid compound dispersions according to Examples 1 to 19 and Comparative Examples 1 to 4 was measured using an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) after confirming that the liquid temperature was stabilized at 25°C. "Initial pH" in Fig. 3 refers to the pH of the metal acid compound dispersions whose temperature was adjusted to 25°C immediately after production. "pH over time" in Fig. 3 refers to the pH of the metal acid compound dispersions according to Examples 1 to 19 and Comparative Examples 1 to 4 after they were left to stand for one month from the day of production in an incubator set at room temperature of 25°C.

[0319] Dynamic Light Scattering The particle size distribution was evaluated by a dynamic light scattering method according to JIS Z 8828:2019 using a zeta potential, particle size, and molecular weight measurement system (ELSZ-2000 manufactured by Otsuka Electronics Co., Ltd.). In addition, immediately before the measurement, in order to remove dust and the like from the metal acid compound dispersion liquid according to Examples 1 to 19, which is the measurement target, the dispersion liquid was filtered through a filter with a pore size of 1 μm. Furthermore, D50 indicates the particle diameter that reaches 50% in terms of volume fraction. "Initial particle diameter D50 (nm)" in FIG. 3 refers to the particle diameter (D50) of the particles in the metal acid compound dispersion liquid immediately after it is generated. In addition, "particle diameter over time D50 (nm)" in FIG. 3 refers to the particle diameter (D50) of the particles in the metal acid compound dispersion liquid after it is left standing for one month from the day of generation of the metal acid compound dispersion liquid according to Examples 1 to 19 and Comparative Examples 1 to 4 in an incubator set at room temperature of 25°C. In addition, for the metal acid compound dispersions according to Comparative Examples 1 to 3, measurements of the initial particle size D50 (nm) and the particle size over time D50 (nm) were not performed because precipitates were visible in the dispersions immediately after production. Note that the above-mentioned filtering was performed when measuring the "initial particle size D50 (nm)", but not when measuring the "particle size over time D50 (nm)", and only ultrasonic treatment was performed.

[0320] <Transmittance measurement> 3 ml of the metal acid compound dispersions according to Examples 1 to 19 and Comparative Examples 1 to 4 were placed in a synthetic quartz cell with an optical path length of 5 mm, and the transmittance of the metals according to Examples 1 to 19 and Comparative Examples 1 to 4 in the wavelength region of 400 nm to 760 nm (specifically, the transmittance at wavelengths of 400 nm, 600 nm, and 750 nm) was measured using a spectrophotometer under the transmittance measurement conditions described above. The "initial transmittance" in FIG. 3 refers to the transmittance of the metal acid compound dispersions adjusted to a liquid temperature of 25° C. immediately after production. The "temporary transmittance" in FIG. 3 refers to the transmittance of the metal acid compound dispersions according to Examples 1 to 19 and Comparative Examples 1 to 4 after they were left to stand for one month from the day of production in an incubator set at room temperature of 25° C.

[0321] <Film-forming test> The appearance of the coating film formed on the surface of the glass substrate, which is a substitute for the current collector, was evaluated by observing it with an optical microscope. First, the metal acid compound dispersion liquids according to Examples 1 to 19 and Comparative Examples 1 to 4 were left to stand for one month from the day of production of the metal acid compound dispersion liquids according to Examples 1 to 19 and Comparative Examples 1 to 4 in an incubator set at room temperature 25°C. Next, the metal acid compound dispersion liquids according to Examples 1 to 19 and Comparative Examples 1 to 4 after standing for one month were dropped onto a 50 mm x 50 mm glass substrate that had been degreased and washed with acetone and then dried using a syringe while being filtered through a filter with a pore size of 0.22 μm, and then coated by spin coating (700 rpm, 10 seconds, then 1500 rpm, 15 seconds). Then, the coated area was naturally dried to form a coating film on the glass substrate. The glass substrate was observed with an optical microscope (magnification: 40x) in a central 15 mm x 15 mm area of ​​the formed coating film. Those on which no particles were present and a film was formed were evaluated as having excellent film-forming properties and were rated as "○ (GOOD)", and those on which particles were observed were evaluated as having poor film-forming properties and were rated as "× (BAD)".

[0322] As shown in Figures 1 to 3, the metal acid compound dispersions of Examples 1 to 19 contained two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium, and had one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound.When the particle diameter (D50) of the particles in the metal acid compound dispersions measured by dynamic light scattering method in the dispersions was 1000 nm or less, the dispersions had high dispersibility in the dispersion medium and excellent solubility.

[0323] The metal compound dispersion liquids according to Examples 1 to 19 contained two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium, and had one or more elements X selected from the group consisting of alkali metal elements and / or alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound. When the maximum transmittance in the wavelength region of 400 nm to 760 nm was 70%T or more, the dispersion liquid had high dispersibility in the dispersion medium and excellent solubility.

[0324] The metal acid compound dispersions of Examples 1 to 19 had excellent stability over time when the content of metal species M in the metal acid compound dispersions of Examples 1 to 19 was 0.01 mass % or more and 30 mass % or less in terms of metal species M atoms.

[0325] The metal acid compound dispersions of Examples 1 to 19 had excellent stability over time when the phosphorus content in the metal acid compound dispersions of Examples 1 to 19 was 0.01% by mass or more and 10% by mass or less in terms of P atoms.

[0326] The metal acid compound dispersions of Examples 1 to 19 showed excellent stability over time, with no significant difference in particle size over time (D50) compared to the initial particle size (D50) even after one month had passed. Meanwhile, precipitates were observed in the metal acid compound dispersions of Comparative Examples 1 and 2.

[0327] The metal acid compound dispersions according to Examples 1 to 19 had improved stability during long-term storage when the molar ratio x / M of the total amount (x) of one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to the total amount (m) of two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium was 0.01 or more and 10 or less. Furthermore, when the element X is Li, the metal acid compound dispersions according to Examples 1 to 19 had improved stability during long-term storage when the molar ratio Li / m of lithium (Li) to the total amount (m) of the metal species M was 0.01 or more and 10 or less.

[0328] The metal acid compound dispersions according to Examples 1 to 19 had improved stability during long-term storage when the molar ratio x / (P+Cl) of the total amount (x) of one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds was 0.01 or more and 5 or less. Furthermore, when the element X is Li, the metal acid compound dispersions according to Examples 1 to 19 had improved stability during long-term storage when the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds was 0.01 or more and 5 or less.

[0329] The metal acid compound dispersions of Examples 1 to 19 had improved stability during long-term storage when the molar ratio m / (P+Cl) of the total amount (m) of two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds was 0.01 or more and 10 or less.

[0330] The metal acid compound dispersions according to Examples 1 to 19 had excellent stability over time when the pH of the dispersions was 2 or more and 11 or less.

[0331] The metal acid compound films formed from the metal acid compound dispersions of Examples 1 to 19 were observed with an optical microscope to show that the coating films formed from each metal acid compound dispersion contained no coarse particles and had excellent film-forming properties.

[0332] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]

[0333] The metal acid compound dispersion according to the present invention has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. In addition, since the metal acid compound dispersion according to the present invention has excellent storage stability and can suppress the rate of defective products caused by precipitation due to changes over time, it is possible to reduce waste and reduce the energy costs for waste disposal. These points lead to the sustainable management and efficient benefits of natural resources, as well as the achievement of decarbonization (carbon neutrality).

Claims

1. A metal acid compound dispersion liquid containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium, One or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements; a phosphorus compound and / or a chlorine compound; Contains A metal acid compound dispersion, wherein the particle diameter (D50) of particles in the metal acid compound dispersion, as measured by dynamic light scattering, is 1000 nm or less.

2. A metal acid compound dispersion liquid containing two or more metal species M selected from the group consisting of niobium, tantalum, molybdenum, tungsten, and titanium, One or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements; a phosphorus compound and / or a chlorine compound; Contains A metal oxide compound dispersion liquid, characterized in that the maximum transmittance in the wavelength region of 400 nm to 760 nm is 70% T or more.

3. 3. The metal acid compound dispersion according to claim 1, wherein the metal species M contains tantalum.

4. 3. The metal acid compound dispersion liquid according to claim 1, wherein the element X contains Li.

5. 3. The metal acid compound dispersion according to claim 1, wherein the phosphorus compound contains at least one selected from the group consisting of inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

6. The metal acid compound dispersion liquid according to claim 5, characterized in that the phosphorus compound contains one or more compounds selected from the group consisting of phosphoric acid, condensed phosphoric acid, pyrophosphoric acid, polyphosphoric acid, phosphorous acid, hypophosphorous acid, ammonium phosphate, primary ammonium phosphate, secondary ammonium phosphate, ammonium pyrophosphate, and ammonium polyphosphate.

7. 3. The metal acid compound dispersion according to claim 1, further comprising hydrogen peroxide.

8. 3. The metal acid compound dispersion according to claim 1, further comprising ammonia and / or an organic nitrogen compound.

9. 3. The metal acid compound dispersion according to claim 1, wherein the content of the metal species M in the metal acid compound dispersion is 0.01% by mass or more and 30% by mass or less in terms of metal species M atoms.

10. 3. The metal acid compound dispersion liquid according to claim 1, wherein the phosphorus content in the metal acid compound dispersion liquid is 0.01% by mass or more and 10% by mass or less in terms of P atoms.

11. 3. The metal acid compound dispersion liquid according to claim 1, wherein a molar ratio x / m of a total amount (x) of the element X to a total amount (m) of the metal species M in the metal acid compound dispersion liquid is 0.01 or more and 10 or less.

12. 3. The metal acid compound dispersion according to claim 1, wherein the element X in the metal acid compound dispersion is Li, and a molar ratio Li / m of lithium (Li) to a total amount (m) of the metal species M is 0.01 or more and 10 or less.

13. 3. The metal acid compound dispersion liquid according to claim 1, wherein a molar ratio x / (P+Cl) of a total amount (x) of the element X to a total amount (P+Cl) of the phosphorus compounds and / or the chlorine compounds in the metal acid compound dispersion liquid is 0.01 or more and 5 or less.

14. 3. The metal acid compound dispersion according to claim 1, wherein the element X in the metal acid compound dispersion is Li, and a molar ratio Li / (P+Cl) of lithium (Li) to a total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is 0.01 or more and 5 or less.

15. 3. The metal acid compound dispersion liquid according to claim 1, wherein the molar ratio m / (P+Cl) of the total amount (m) of the metal species M in the metal acid compound dispersion liquid to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is 0.01 or more and 10 or less.

16. 3. The metal acid compound dispersion according to claim 1, wherein the metal acid compound dispersion is an aqueous dispersion.

17. 3. The metal acid compound dispersion according to claim 1, wherein the particle diameter (D50) of particles in the metal acid compound dispersion measured by dynamic light scattering method is 100 nm or less.

18. 3. The metal acid compound dispersion according to claim 1, wherein the metal acid compound dispersion has a pH of 2 or more and 11 or less.

19. A metal acid compound powder comprising the metal acid compound in the metal acid compound dispersion liquid according to claim 1 or 2.

20. A metal acid compound film comprising the metal acid compound in the metal acid compound dispersion liquid according to claim 1 or 2.

21. A coating agent comprising the metal acid compound dispersion liquid according to claim 1 or 2.

22. A coating agent comprising the metal acid compound powder according to claim 19.

23. 3. The metal acid compound dispersion according to claim 1, which is used for a positive electrode of a lithium ion secondary battery or for coating a positive electrode material.

24. 3. A positive electrode active material for a lithium ion secondary battery, the surface of which is coated with the metal acid compound contained in the metal acid compound dispersion liquid according to claim 1 or 2.

25. A lithium ion secondary battery comprising a positive electrode having a surface coated with the positive electrode active material for lithium ion secondary batteries according to claim 24.

Citation Information

Patent Citations

  • Tantalum oxide sol and its production

    JP1996143315A

  • Sol-gel composite piezoelectric sensor production method

    JP2023063187A

Cited By

  • Coated particles and method for manufacturing same

    WO2026186708A1